Organic modified metal oxide or metalloid oxide polymer film
By preparing and treating precursor compositions of metal or metalloid compounds under low temperature conditions, the problems of high temperature treatment and excessive HCl release in the prior art are solved, and a high refractive index and stable metal oxide or metalloid oxide polymer film is achieved.
Patent Information
- Application Number
- CN202510075678.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-02-23
- Filing Date
- 2019-02-21
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art has problems such as high processing temperature, excessive HCl release and insufficient refractive index when preparing metal oxide or metal quasi-oxide polymer films, which limits the application range and performance of the material.
By preparing a precursor composition containing a metal or metalloid compound, and mixing and curing it under low temperature conditions, a high refractive index metal oxide or metalloid oxide polymer film is formed. This method avoids high temperature treatment and release of HCl, and increases the refractive index of the film.
It is possible to prepare high-refractive index metal oxide or metal quaso-oxide polymer films at low temperatures, avoiding thermal damage to the material layer, and improving the stability and optical properties of the film.
Smart Images

Figure BDA0005247007030000121 
Figure BDA0005247007030000401 
Figure BDA0005247007030000411
Abstract
Description
[0001] This application is a divisional application of a patent application with application number 201980014109.1, application date February 21, 2019, and invention name “Organically modified metal oxide or metalloid oxide polymer film”.
[0002] The present invention relates to a method for preparing an organically modified metal oxide or metalloid oxide polymer film, a coating composition, an article comprising the coating and use of the coating composition for preparing a coating.
[0003] As is known in the art, organically modified silica can be used to form optically transparent and well electrically insulating layers by using it as an organosiloxane polymer (also known as a "sol-gel polymer"). For example, in the simplest case, tetraethoxysilane or silicon tetrachloride is hydrolyzed, and the polycondensation of the hydrolyzed monomers produces a siloxane polymer that can be converted into a silica material under thermal treatment. In addition, organosiloxanes can be made photolithographically patternable by covalently attaching a photocrosslinking moiety to the silica backbone. However, silicon oxide materials based on pure silica or even organically modified silica exhibit a relatively low refractive index. The refractive index of these materials is generally not higher than 1.5, and their dielectric constants are between about 4.2 and 2.5 depending on their structure and on the moieties attached to silicon.
[0004] Known are hybrid metal oxide materials (e.g. titanium oxide hybrid polymers) (EP1761462B1), which can be obtained by hydrolyzing metal halide or alkoxide precursors in solution. The obtained formulation can be applied by, for example, spin coating. The resulting film is suitable for further processing by photolithography, embossing, roll-to-roll printing / coating or gravure printing / coating. When organic monomers (e.g. methacrylates) are present in the formulation, the material is suitable for use as a negative resist in a photolithography process, because the unexposed parts can be washed off with an alkaline developer solution after UV irradiation. The processing temperature is 350-500°C.
[0005] WO 2006 / 134218A1 discloses an optical device structure comprising a photonic crystal coated with alternating layers of high and low refractive index, wherein the coating is obtainable from reactive metal oxide precursors, such as halides or alkoxides of Ge, Ti, Sn, Sb, Ta, Hf, Zr and Si. The layers are deposited from the liquid phase and can be patterned in a photolithographic process. A processing temperature of 250-400° C. is disclosed.
[0006] A disadvantage of the aforementioned procedure is that large amounts of HCl are released during the formulation process, which requires neutralization, removal and disposal.
[0007] In addition, the processing temperature is high, which makes the underlying material layer susceptible to thermal damage and limits the application of the polymer as a film on materials that can withstand high processing temperatures. Therefore, a composition that can be processed at a temperature below 400°C, preferably even below 100°C, is desirable. In addition, the material should be suitable for thermal curing only, combined thermal and UV curing, or UV curing only. UV-curing systems only are usually solvent-free or almost solvent-free, which means that we need to introduce a material platform that is essentially solvent-free. In this system, no organic solvents can be present to damage the underlying device layers, and minimal or even no volatiles can be released during the curing process.
[0008] Furthermore, the refractive index should be higher than 1.5 at 632 nm.
[0009] It has been found that the above-mentioned object can be achieved by the following method provided by the present invention.
[0010] A method for preparing a thin film on a substrate, the method comprising the following steps:
[0011] a) preparing a first precursor composition (FPC) in a first container, the preparation comprising the following steps:
[0012] a1) providing one or more metal or metalloid compounds according to the following formula (I):
[0013] M 1 (OR 1 ) n R 2 m (I)
[0014] in:
[0015] M 1 is a metal or metalloid with a valence state z,
[0016] R 1 Each independently selected from C 1 -C 10 an organic group or an organic heteroatom group,
[0017] R 2 Each independently selected from C 1 -C 20 an organic group or an organic heteroatom group,
[0018] n is 1 to z,
[0019] m is z-1 to 0,
[0020] n+m is z,
[0021] a2) at least partially hydrolyze M 1 (OR 1) moiety and polymerizes a metal or metalloid compound according to formula (I);
[0022] b) preparing a second precursor composition (SPC) in a second container, the preparation comprising the following steps:
[0023] b1a) providing a metal or metalloid compound according to the following formula (II):
[0024] M 2 (OR 3 ) o (II)
[0025] in:
[0026] M 2 is a metal or metalloid with a valence state y, where M 1 and M 2 Based on the different elements of the periodic table,
[0027] R 3 Each independently selected from C 1 -C 10 an organic group or an organic heteroatom group,
[0028] o is y;
[0029] b2a) optionally, mixing a metal or metalloid compound according to formula (II) with a metal or metalloid compound different from (OR 3 ) of a ligand (L); or
[0030] b1b) directly providing the reaction product of step b2a);
[0031] c) mixing the first precursor composition (FPC) with the second precursor composition (SPC);
[0032] c1) optionally, reacting the product of step c) with Si(R 23 ) 3 X reaction, where:
[0033] R 23 C 1 -C 3 alkyl,
[0034] X represents Cl or OR 24 ,
[0035] R 24 C 1 -C 3 alkyl;
[0036] d) forming a thin layer on a substrate;
[0037] e) optionally, after step d), partially or completely removing the solvent, if present;
[0038] f) solidifying the intermediate product obtained in step e) if present or in step d) if no step e) is present;
[0039] Wherein, optionally, (meth)acrylate (ME) is added at the following time:
[0040] - during the preparation of the first precursor composition (FPC),
[0041] - during the preparation of the second precursor composition (SPC), and / or
[0042] - during step c) or after step c) and before carrying out step d).
[0043] The film thus obtained provides a higher refractive index and can be applied at low temperatures. In addition, since particles are not required for the preparation of the film or particles are not caused during the preparation of the film, defects caused by particles will not occur in the film of the present invention. The film of the present invention has a combined out-coupling and a thin film encapsulation layer and a planarization capability. Planarization and particle-free are extremely important for higher resolution displays with smaller and smaller pixel sizes and densities. In addition, the film is long-term stable and provides a combined improvement in transmission and refractive index. In addition, the composition can be used in a diluted form, for example, for inkjet printing, slit coating or as a solvent-free system. In both cases, it can be applied by conventional methods (such as slit coating and inkjet printing). If necessary, the film of the present invention can be used together with scattering particles, for example, for OLED lighting, where the layer can be used as a scattering layer. However, particle defects will not be generated or only very few particle defects will be generated.
[0044] Unless explicitly stated to the contrary, the following definitions apply in the present invention.
[0045] An organic group is an organic substituent having one free valence at a carbon atom.
[0046] An organic heteroatom radical is an organic substituent having one free valence at an atom other than a carbon atom.
[0047] First Precursor Composition
[0048] As described above, a first precursor composition (FPC) is prepared in a first container, the preparation comprising the following steps:
[0049] a1) providing one or more metal or metalloid compounds according to the following formula (I):
[0050] M1 (OR 1 ) n R 2 m (I)
[0051] in:
[0052] M 1 is a metal or metalloid with a valence state z,
[0053] R 1 Each independently selected from C 1 -C 10 an organic group or an organic heteroatom group,
[0054] R 2 Each independently selected from C 1 -C 20 an organic group or an organic heteroatom group,
[0055] n is 1 to z,
[0056] m is z-1 to 0,
[0057] n+m is z;
[0058] a2) at least partially hydrolyze M 1 (OR 1 ) structural part and polymerize one or more metals or
[0059] Metalloid compounds.
[0060] In step a1), up to five different metal or metalloid compounds according to formula (I) may be provided, typically not more than three different metal or metalloid compounds according to formula (I) are provided.
[0061] Preferably, the one or more metal or metalloid compounds according to formula (I) are fluorine-free. Thus, in case more than one metal or metalloid compound according to formula (I) is provided, they are preferably all fluorine-free. More preferably, no fluorine-containing compounds other than the optional fluorine-containing solvent are present during the preparation of the first precursor composition (FPC) before the implementation of step c), even more preferably, in the case of the presence of a solvent, the amount of the fluorine-containing solvent is equal to or less than 75% by weight based on the total weight of the solvent present, most preferably, no fluorine-containing compounds including the fluorine-containing solvent are present during the preparation of the first precursor composition (FPC) before the implementation of step c).
[0062] M 1 Preferably, it is selected from Si, Ge, Sb, Ti, Zr, Al, Sn, W, Se, Cr, Ag or Ni, more preferably selected from Si, Ti, Zr, Ge, Sb, and most preferably M 1 For Si.
[0063] R 1 Each independently selected from C 1 -C 10 An organic group or an organic heteroatom group.
[0064] In the presence of heteroatoms in R 1 In the case of an organic group, it is preferably selected from N, O, P, S or Si, more preferably selected from N and O.
[0065] Preferred group OR 1 It is an alkoxy group, an acyloxy group and an aryloxy group.
[0066] R bonded to oxygen atom 1 The heteroatom of the organic heteroatom group is usually different from O, and the oxygen atom is bonded to M 1 .
[0067] Exists in R 1 The heteroatom in the organic heteroatom group is preferably selected from N, O, P or S, more preferably from N and O.
[0068] If it exists, then R 1 The total number of heteroatoms in is usually not more than 5, preferably not more than 3.
[0069] Preferably, R 1 A C containing no more than 3 heteroatoms 1 -C 10 The organic group, more preferably, R 1 C 1 -C 10 The hydrocarbon group is, even more preferably, C 1 -C 10 Straight-chain, branched or cyclic alkyl groups.
[0070] Preferably, R present in any of the above variants 1 The total number of carbon atoms in is 1-6, more preferably 1-4.
[0071] R 2 Each independently selected from C 1 -C 20 An organic group or an organic heteroatom group.
[0072] In the presence of heteroatoms in R 2 In the case of an organic group, it is preferably selected from N, O, P, S or Si, more preferably selected from N and O.
[0073] Key to M 1 R 2 The heteroatom of the organic heteroatom group is usually different from O.
[0074] Exists in R 2 The heteroatom in the organic heteroatom group is preferably selected from N, O, P or S, more preferably from N and O.
[0075] If it exists, then R 2 The total number of heteroatoms in is usually no more than 8, preferably no more than 5, most preferably no more than 3.
[0076] Preferably, R 2 A C containing no more than 3 heteroatoms 1 -C 20 The organic group, more preferably, R 2 Selected from C 1 -C 20 Hydrocarbon, C 1 -C 20 Mercaptoalkyl, C 1 -C 20 Hydrocarbyl (meth)acrylate and C 1 -C 20 Hydrocarbyl glycidyl ether, more preferably C 1 -C 20 Alkyl, C 1 -C 20 Mercaptoalkyl, C 1 -C 20 Alkyl (meth) acrylate group and C 1 -C 20 In the above variants, the number of carbon atoms given represents R 2 The total number of carbon atoms present in R 2 In the case of a 3-methacryloyloxy group, the number of carbon atoms is 7.
[0077] Preferably, R present in any of the above variants 2 The total number of carbon atoms in is 1-15, more preferably 1-10, most preferably 1-7.
[0078] Preferably, n is at least 2. In the metal or metalloid M 1 In the case where the valence z is 4 or greater, n is preferably at least 3.
[0079] Preferably, in at least one compound according to formula (I), each R, if present, 1 and R 2 Therefore, R 1 and R 2 Still can be different.
[0080] More preferably, in each compound according to formula (I), if present, each R 1 and R 2Therefore, in the case where more than one compound according to formula (I) is used, R of one compound according to formula (I) 1 can still be combined with another compound according to formula (I) 1 different.
[0081] In case more than one compound according to formula (I) is provided in step a1), preferably in at least one compound according to formula (I), n=z, and in at least one other compound according to formula (I), n=z. <z。
[0082] Suitable compounds according to formula (I) are, for example, triethoxysilane, tetraethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane, dimethyldiethoxysilane, diethyldiethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, n-butyltriethoxysilane, methyldiethoxyvinylsilane, phenyltrimethoxysilane, phenanthrene-9-triethoxysilane, vinyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, aminopropyltrimethoxysilane, n-hexyltrimethoxysilane, propyltrimethoxysilane, methacryloxypropyltrimethoxysilane, methacryloxypropylmethyldimethoxysilane, methacryloxypropyltrimethoxysilane, trimethoxysilane, methoxydimethylsilane, ethoxydimethylsilane, n-propoxytrimethylsilane, methoxydimethylethylsilane, ethoxydimethylethylsilane, n-propoxydimethylethylsilane, methoxydimethylvinylsilane, ethoxydimethylvinylsilane, n-propoxydimethylvinylsilane, trimethoxymethylsilane and triethoxymethylsilane, and mixtures thereof.
[0083] In step a2), a compound according to the following formula (III) may be present:
[0084] R 7 ' t' (OR 6 ') s' M 3 ' - YM 3 (OR 6 ) s R7 t (III)
[0085] in:
[0086] M 3 、M 3 'same or different and each independently selected from metals or metalloids having a valence state x;
[0087] Y is a divalent linking group;
[0088] R 6 , R 6 'same or different and each independently selected from C 1 -C 10 an organic group or an organic heteroatom group;
[0089] R 7 , R 7 'same or different and each independently selected from C 1 -C 20 An organic group or an organic heteroatom group; s, s' are the same or different and are each independently selected from 1 to x-1;
[0090] t, t' are the same or different and are each independently selected from x-2 to 0;
[0091] s+t is x-1; and
[0092] s'+t' is x-1.
[0093] In case a compound according to formula (III) is present in step a2), preferably, this compound is provided in a further step a1a), which can be carried out before, after or together with step a1).
[0094] M 3 and M 3 ' is preferably selected from Si, Ge, Sb, Ti, Zr, Al, Sn, W, Se, Cr, Ag or Ni, more preferably selected from Si, Ti, Zr, Ge, Sb, and most preferably Si.
[0095] Preferably, M 3 and M 3 'same.
[0096] R 6 , R 6 'same or different and each independently selected from C 1 -C 10 An organic group or an organic heteroatom group.
[0097] In the presence of heteroatoms in R 6 and / or R 6In the case of an organic group of ', it is preferably selected from N, O, P, S or Si, more preferably selected from N and O.
[0098] Preferably, the group OR 6 and / or 6 ' is alkoxy, acyloxy and aryloxy.
[0099] R bonded to oxygen atom 6 and / or R 6 The heteroatom of the organic heteroatom group is usually different from O, and the oxygen atom is bonded to M 3 or M 3 '.
[0100] Exists in R 6 and / or R 6 The heteroatom in the organic heteroatom group of ' is preferably selected from N, O, P or S, more preferably selected from N and O.
[0101] If it exists, then R 6 and / or R 6 The total number of heteroatoms in ' is usually not more than 5, preferably not more than 3.
[0102] Preferably, R 6 and / or R 6 ' is a C containing no more than 3 heteroatoms 1 -C 10 The organic group, more preferably, R 6 and / or R 6 ' is C 1 -C 10 The hydrocarbon group is, even more preferably, C 1 -C 10 Straight-chain, branched or cyclic alkyl groups.
[0103] Preferably, R present in any of the above variants 6 and / or R 6 The total number of carbon atoms in ' is 1-6, more preferably 1-4.
[0104] Preferably, R 6 and R 6 'same.
[0105] R 7 , R 7 'Each independently selected from C 1 -C 20 An organic group or an organic heteroatom group.
[0106] In the presence of heteroatoms in R 7 and / or R 7In the case of an organic group of ', it is preferably selected from N, O, P, S or Si, more preferably selected from N and O.
[0107] Key to M 3 or M 3 'R 7 and / or R 7 The heteroatom of the organic heteroatom group is usually different from O.
[0108] Exists in R 7 and / or R 7 The heteroatom in the organic heteroatom group of ' is preferably selected from N, O, P or S, more preferably selected from N and O.
[0109] If it exists, then R 7 and / or R 7 The total number of heteroatoms in ' is usually not more than 8, preferably not more than 5, most preferably not more than 3.
[0110] Preferably, R 7 and / or R 7 ' is a C containing no more than 3 heteroatoms 1 -C 20 The organic group, more preferably, R 7 and / or R 7 ' is C 1 -C 20 The hydrocarbon group is, even more preferably, C 1 -C 20 Straight-chain, branched or cyclic alkyl groups.
[0111] Preferably, R present in any of the above variants 7 and / or R 7 The total number of carbon atoms in ' is 1-15, more preferably 1-10, most preferably 1-6.
[0112] Preferably, R 7 and R 7 'same.
[0113] Preferably, s and / or s' is at least 2. 3 and / or M 3 In the case where the valence z of ' is 4 or more, s and / or s' is preferably at least 3.
[0114] Suitable compounds according to formula (III) are, for example, 1,2-bis(trimethoxysilyl)methane, 1,2-bis(triethoxysilyl)methane, 1,2-bis(trimethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethane, 1-(dimethoxymethylsilyl)-1-(trimethoxysilyl)methane, 1-(diethoxymethylsilyl)-1-(triethoxysilyl)methane, 1-(trimethoxymethylsilyl)-2-(dimethoxysilyl)ethane, 1-(dimethoxymethylsilyl)-2-(trimethoxysilyl)ethane, bis(dimethoxymethylsilyl)methane, Bis(diethoxymethylsilyl)methane, 1,2-bis(dichloromethylsilyl)ethane, 1,2-bis(trichlorosilyl)ethane, 1,2-bis(dimethoxymethylsilyl)ethane, 1,2-bis(diethoxymethylsilyl)ethane, 1,2-bis(trimethoxysilyl)benzene, 1,2-bis(triethoxysilyl)benzene, 1,3-bis(trimethoxysilyl)benzene, 1,3-bis(triethoxysilyl)benzene, 1,4-bis(trimethoxysilyl)benzene, 1,4-bis(triethoxysilyl)benzene, 4,4'-bis(triethoxysilyl)-1,1'-biphenyl, 1,4-bis(triethoxysilyl)benzene and 1,3-bis(triethoxysilyl)benzene, and combinations thereof.
[0115] The at least partial hydrolysis in step a2) is preferably carried out under acidic or alkaline conditions, usually using a catalyst such as sulfuric acid, hydrochloric acid, nitric acid, acetic acid, citric acid, formic acid, trifluoromethanesulfonic acid, perfluorobutyric acid or other inorganic or organic acids or bases, more preferably inorganic acids such as HNO 3 .
[0116] When an acid is used, the concentration of the acid is preferably 0.01-1.0 mol / l, more preferably 0.05-0.2 mol / l. The acid is usually dissolved in water or a mixture of water and an organic solvent, such as an alcohol, a ketone, preferably a ketone, such as acetone.
[0117] The at least partial hydrolysis in step a2) is preferably carried out at a temperature of 5 to 150° C. but not above the boiling point of the solvent or solvent mixture present in step a2).
[0118] The at least partial hydrolysis in step a2) is preferably carried out for 1.0 to 10 hours, preferably 2.5 to 7.5 hours.
[0119] During the at least partial hydrolysis in step a2), a basic substance, such as an amine, such as C 1 -C 4 Trialkylamine.
[0120] Preferably, the molecular weight of the product of step a2) is 250-6000 g / mol, more preferably 500-1500 g / mol.
[0121] During the preparation of the first precursor composition, one or more additional organic solvents may be used.
[0122] Preferably, the solvent is selected from: alcohols, which preferably contain 1-6 carbon atoms, such as methanol, ethanol, propanol, butanol; ether alcohols, such as propylene glycol monomethyl ether; ketones, such as acetone; esters, such as propylene glycol monomethyl ether acetate, ethyl acetate, methyl formate; and ethers, such as diethyl ether, THF; preferably an alcohol, an ether alcohol or a ketone.
[0123] A mixture of up to 5 organic solvents may be used, preferably no more than 3 organic solvents are used, and most preferably only one organic solvent is used.
[0124] Preferably, as described above, the organic solvent used during the preparation of the first precursor composition does not contain fluorine.
[0125] More preferably, after step a2), a further step a3) is performed.
[0126] a3) in the case of the presence of a solvent in step a2), by one or more organic solvents as described above
[0127] to replace one or more solvents used in step a2), or
[0128] In case a solvent is present in step a2), the solvent is removed.
[0129] In case the at least partial hydrolysis in step a2) is carried out using a catalyst, in each variant of step a3) the catalyst can be removed, preferably the catalyst is removed.
[0130] Exchanging solvents means that the solvent or solvent mixture present before and after the solvent exchange is different. Typically, the water typically present in at least part of the hydrolysis in step a2) is removed by solvent exchange.
[0131] Thus, for example, the water and optionally the organic solvent (e.g. a ketone) used in the at least partial hydrolysis of step a2) are replaced by a different organic solvent, e.g. an alcohol, e.g. C 1 -C 4 alcohol.
[0132] More preferably, the solvent is removed in step a3) and optionally, in case the at least partial hydrolysis in step a2) is carried out using a catalyst, the catalyst is removed in each variant of step a3).
[0133] Second Precursor Composition
[0134] As described above, a second precursor composition (SPC) is prepared in a second container, the preparation comprising the following steps:
[0135] b1a) providing a metal or metalloid compound according to the following formula (II):
[0136] M 2 (OR 3 ) o (II)
[0137] in:
[0138] M 2 is a metal or metalloid with a valence state y, where M 1 and M 2 Based on the different elements of the periodic table,
[0139] R 3 Each independently selected from C 1 -C 10 an organic group or an organic heteroatom group,
[0140] o is y;
[0141] b2a) optionally, mixing a metal or metalloid compound according to formula (II) with a metal or metalloid compound different from (OR 3 ) ligand (L)
[0142] reaction; or
[0143] b1b) directly provides the reaction product of step b2a).
[0144] Thus, the metal or metalloid compound according to formula (II) may be used, but preferably before step c) with a metal or metalloid compound different from (OR 3 )'s ligand (L) reaction.
[0145] R 3 Each independently selected from C 1 -C 20 An organic group or an organic heteroatom group.
[0146] In the presence of heteroatoms in R 3 In the case of an organic group, it is preferably selected from N, O, P, S or Si, more preferably selected from N and O.
[0147] Key to M 2 R 3 The heteroatom of the organic heteroatom group is usually different from O.
[0148] Exists in R 3The heteroatom in the organic heteroatom group is preferably selected from N, O, P or S, more preferably from N and O.
[0149] If it exists, then R 3 The total number of heteroatoms in is usually no more than 8, preferably no more than 5, most preferably no more than 3.
[0150] Preferably, R 3 A C containing no more than 3 heteroatoms 1 -C 20 The organic group, more preferably, R 3 C 1 -C 20 The hydrocarbon group is, even more preferably, C 1 -C 20 Straight-chain, branched or cyclic alkyl groups.
[0151] Preferably, R present in any of the above variants 3 The total number of carbon atoms in is 1-15, more preferably 1-10, most preferably 1-6.
[0152] Preferably, each R present 3 same.
[0153] M 2 Preferably, M is selected from Si, Ge, Sb, Ti, Zr, Al, Sn, W, Se, Cr, Ag or Ni, more preferably selected from Si, Ti, Zr, Ge, Sb, and most preferably, M 2 It is Ti and / or Zr.
[0154] Suitable compounds according to formula (II) are, for example, C 1 -C 10 Zirconium (IV) and titanium (IV) compounds of alcohols as OR 3 , where R 3 It is a straight-chain, branched or cyclic aliphatic hydrocarbon, for example zirconium tetramethoxide, zirconium tetraethoxide, zirconium tetrapropoxide, zirconium tetrabutoxide, zirconium acetate, zirconium acetylacetonate, titanium tetramethoxide, titanium tetraethoxide, titanium tetrapropoxide, titanium acetate, titanium tetrabutoxide.
[0155] Different from (OR 3 The ligand (L) of ) is preferably a ligand whose coordinating atom is selected from O, N and S, preferably from O and N, and most preferably from O.
[0156] Different from (OR 3) can be any compound selected from the following group: organic acid, anhydride, alkoxide, ketone, β-diketone, acetylacetone, benzyl acetone, aryl oxide, β-keto ester, alkanolamine, diol, oxime, alkylhydroxylamine, β-ketoamine, Schiff base, thiol and aldehyde. Thus, examples of suitable organic compounds include, but are not limited to, acetic acid, acrylic acid, methacrylic acid, trifluoroacetic acid. Other examples are formed by ketones and aldehydes, such as acetone and β-diketone.
[0157] Typically, the ligand (L) has a molecular weight of no more than 1000 g / mol, more preferably no more than 750 g / mol, most preferably no more than 500 g / mol.
[0158] Different from (OR 3 Suitable ligands (L) for use in the invention are for example compounds according to formula (III) as defined above or compounds according to the following formulae (IV), (IV'), (VI") and (IV'"):
[0159]
[0160] in:
[0161] R 8 , R 9 The same or different and each independently selected from C 1 -C 10 Organic group or C 1 -C 10 An organic heteroatom group, preferably C 1 -C 10 Hydrocarbon, C 1 -C 10 The alkyloxy group is preferably a linear, branched or cyclic C 1 -C 10 Alkyl, C 6 -C 10 Aryl, C 1 -C 10 Alkoxy, C 6 -C 10 Aryloxy and C 7 -C 10 Alkyl aryloxy, most preferably linear, branched or cyclic C 1 -C 10 Alkyl and C 1 -C 10 Alkoxy;
[0162] R 10 , R 11 are the same or different and are each independently selected from hydrogen, C 1 -C 4 Organic group or C 1 -C4 The organic heteroatom group is preferably selected from hydrogen and C 1 -C 4 Hydrocarbyl, most preferably selected from hydrogen and C 1 -C 4 Alkyl groups, such as hydrogen;
[0163] R 20 C 2 -C 6 Alkylene, which may be interrupted by O or NR 22 ;
[0164] R 21 are independently selected from hydrogen or C 1 -C 6 Hydrocarbyl, preferably C 1 -C 6 alkyl;
[0165] R 22 It is hydrogen, methyl or hydroxyethyl.
[0166] Preferably, different from (OR 3 ) is a bidentate or multidentate ligand (L), more preferably a bidentate ligand, for example selected from the above formula (IV), (IV') and (IV''), preferably selected from the above formula (IV) or (IV'), most preferably selected from the above formula (IV).
[0167] In the presence of heteroatoms in R 8 , R 9 , R 10 and R 11 In the case of an organic group, it is preferably selected from N, O, P, S or Si, more preferably selected from N and O.
[0168] Exists in R 8 , R 9 , R 10 and R 11 The heteroatom in the organic heteroatom group is preferably selected from N, O, P or S, more preferably from N and O.
[0169] If it exists, then R 8 and R 9 The total number of heteroatoms in is usually no more than 5, preferably no more than 3, most preferably no more than 1.
[0170] If it exists, then R 10 and R 11 The total number of heteroatoms in is usually not more than 2, preferably not more than 1.
[0171] During the preparation of the second precursor composition, one or more organic solvents may be used.
[0172] Preferably, the solvent is selected from: alcohols, which preferably contain 1-6 carbon atoms, such as methanol, ethanol, propanol, butanol; ether alcohols, such as propylene glycol monomethyl ether; ketones, such as acetone; esters, such as propylene glycol monomethyl ether acetate, ethyl acetate, methyl formate; and ethers, such as diethyl ether, THF; preferably an alcohol, an ether alcohol or a ketone.
[0173] A mixture of up to 5 organic solvents may be used, preferably no more than 3 organic solvents are used, and most preferably only one organic solvent is used.
[0174] In case step b2a) is present, the reaction time is preferably from 1.0 hour to 10 days, more preferably from 2.5 to 7.5 days.
[0175] In case step b2a) is present, the reaction temperature generally does not exceed 75°C, more preferably does not exceed 50°C.
[0176] More preferably, after step b1a), or if step b2a) is present, after step b2a), or if step b1b) is present, after step b1b), an additional step b3) is performed. b3) In any of steps b1a), b2a) (if present), b1b) (if present) the solvent is present.
[0177] In the case of the above, the one or more solvents present after steps b1a), b2a) (if present), b1b) (if present) are replaced by one or more organic solvents as described above,
[0178] or
[0179] In case a solvent is present in any of steps b1a), b2a) (if present), b1b) (if present), the solvent is removed.
[0180] Preferably, the solvent is replaced, more preferably, by removing the solvent present in any of steps b1a), b2a) (if present), b1b) (if present), and adding solvent. The solvent present before and after the solvent replacement may be the same compound, especially in the case where the solvent is removed and a new solvent is added. This is particularly preferred in the case where step b2a) is present.
[0181] Step c)
[0182] During step c), the first precursor composition (FPC) is combined with the second precursor composition (SPC).
[0183] Additional organic solvent may be added during step c) to obtain the desired final solids content.
[0184] Preferably, the solvent that can be added is selected from: alcohols, which preferably contain 1-6 carbon atoms, such as methanol, ethanol, propanol, butanol, ether alcohols, such as propylene glycol monomethyl ether, dipropylene glycol, ethylene glycol, ketones, esters, such as ethyl acetate, methyl formate; ethers, propylene glycol methyl ether; particularly preferred are alcohols, which preferably contain 1-6 carbon atoms, such as methanol, ethanol, propanol, ethylene glycol, propylene glycol methyl ether or mixtures thereof; most preferably selected from alcohols, which preferably contain 1-6 carbon atoms, such as methanol, ethanol, propanol, butanol, ether alcohols, such as propylene glycol monomethyl ether, dipropylene glycol, propylene glycol monomethyl ether acetate, tetrahydrofurfuryl alcohol, cyclohexanone, ethylene glycol or propylene glycol methyl ether.
[0185] In step c), the weight ratio of the solid content of the first precursor composition (FPC) to the solid content of the second precursor composition (SPC) is preferably 10:1.0 to 1.0:2000, preferably 5.0:1.0 to 1.0:1500.0, more preferably 2.0:1.0 to 1.0:500.0.
[0186] Preferably, in step c), M 1 With M 2 The molar ratio is 1.0:10 to 10:1.0, preferably 1.0:10 to 1.0:1.0, and more preferably 1.0:10 to 1.0:2.0.
[0187] As mentioned above, the method optionally comprises the following steps:
[0188] c1) reacting the product of step c) with Si(R 23 ) 3 X or Si(R 23 ) 2 X 2 Reaction, where:
[0189] R 23 C 1 -C 3 alkyl,
[0190] X represents Cl or OR 24 ,
[0191] R 24 C 1 -C 3 alkyl.
[0192] In the optional step c1), the second precursor composition (SPC) is reacted with Si (R 23 ) 3 The molar ratio of X is preferably from 100:1.0 to 1.0:20, preferably from 10.0:1.0 to 1.0:5.0, more preferably from 5.0:1.0 to 1.0:2.0.
[0193] The reaction temperature of c1) is 25-150° C., preferably 60-120° C. The reaction time is usually 0.1 hour to 5 days, more preferably 0.5-24 hours.
[0194] Furthermore, conventional additives for the coating composition of the film may be added during step c). Such conventional additives include, for example, surfactants, leveling agents, processing aids, antistatic agents, antioxidants, water and oxygen scavengers, catalysts, photoinitiators or mixtures thereof. In some cases, it may also be preferred to introduce scattering particles into the film coating solution. Such particles generally provide additional optical effects, for example to meet specific requirements, for example for lighting applications. These particles may, for example, be SiO 2 、TiO 2 、ZrO 2 Or similar inorganic particles.
[0195] Examples of photoinitiators which can be added in step c) are free radical photoinitiators, for example camphorquinone; benzophenone, benzophenone derivatives; ketal compounds, such as, for example, benzyldicarboxaldehyde acetophenone acetal (Omnirad 651); acetophenone, acetophenone derivatives, for example, α-hydroxycycloalkylphenyl ketone or α-hydroxyalkylphenyl ketone, for example, 2-hydroxy-2-methyl-1-phenylpropanone (Omnirad 1173), 1-hydroxycyclohexylphenyl ketone (Omnirad 184), 1-(4-dodecylbenzoyl)-1-hydroxy-1-methylethane, 1-(4-isopropylbenzoyl)-1-hydroxy-1-methylethane, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one (Omnirad 185). 2-Hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)-benzyl]-phenyl}-2-methyl-propan-1-one (Omnirad 127); 2-Hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)-phenoxy]-phenyl}-2-methyl-propan-1-one; dialkoxyacetophenones, α-hydroxyaminoacetophenones or α-aminoacetophenones, for example (4-methylthiobenzoyl)-1-methyl-1-morpholinoethane (Omnirad 907), (4-morpholinobenzoyl)-1-benzyl-1-dimethylaminopropane (Omnirad 369), (4-morpholinobenzoyl)-1-(4-methylbenzyl)-1-dimethylaminopropane (Omnirad 506). 379), (4-(2-hydroxyethyl)aminobenzoyl)-1-benzyl-1-dimethylaminopropane), (3,4-dimethoxybenzoyl)-1-benzyl-1-dimethylaminopropane; 4-aroyl-1,3-dioxolanes, benzoin alkyl ethers and benzyl ketals, such as dimethylbenzyl ketal, phenylglyoxylic acid esters and derivatives thereof, such as 2-(2-hydroxy-ethoxy)-ethyl oxyphenylacetate, diphenylglyoxylic acid esters, such as 1-methyl-2-[2-(2-oxo-2-phenylacetoxy)-propoxy]-ethyl oxyphenylacetate (Omnirad 754); oxime esters, such as 1,2-octanedione 1-[4-(phenylthio)phenyl]-2-(O-benzoyl oxime) ( OXE01), ethyl ketone 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-1-(O-acetyl oxime) ( OXE02), ketone [8-[[(acetyloxy)imino][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methyl]-11-(2-ethylhexyl)-11H-benzo[a]carbazole-5-yl](2,4,6-trimethylphenyl), [(E)-[1-[4-[4-(benzofuran-2-carbonyl)phenyl]sulfanylphenyl]-4-methylpentylidene]amino]acetate, ethyl ketone 1-[9-ethyl-6-(2-methyl-4-(2,2-dimethyl-1,3-dioxolanyl)methoxybenzoyl)-9H-carbazole-3 -yl]-1-(O-acetoxime), N-acetoxy-N-{3-[9-ethyl-6-(naphthalene-1-carbonyl)-9H-carbazol-3-yl]-1-methyl-3-acetoxyiminopropyl}-acetamide, 9H-thioxanthen-2-carbaldehyde 9-oxo-2-(O-acetoxime), [(E)-[1-(cyclohexylmethyl)-2-oxo-2-(4-phenylsulfanylphenyl)ethylidene]amino]cyclopropanecarboxylate), [(E)-[1-(cyclohexylmethyl)-2-oxo-2-(4-phenylsulfanylphenyl)ethylidene]amino]acetate, [(E)-[1-(cyclohexylmethyl)-2-oxo-2-(4-phenylsulfanylphenyl)ethylidene]amino]acetate [(E)-1-[9-ethyl-6-(thiophene-2-carbonyl)carbazole-3-yl]-2-oxo-ethylidene]amino]acetate, [(E)-[1-(o-tolyl)-2-oxo-2-(4-phenylsulfanylphenyl)ethylidene]amino]acetate, [(E)-1-[1-(4-benzoylphenyl)indole-3-carbonyl]heptyleneamino]acetate, [(E)-1-[9-ethyl-6-(thiophene-2-carbonyl)carbazole-3-yl]ethylideneamino]acetate, [(E)-1-[9-ethyl-6-(thiophene-2-carbonyl)carbazole-3-yl]ethylideneamino]acetate, [(E)-1-(9,9-dibutyl-7-nitro-fluoren-2-yl)ethylideneamino]acetate, [(Z)-[2-(9,9-diethylfluoren-2-yl)-1-methyl-2-oxoethylidene]amino]acetate, oxime esters described in WO07 / 062963, WO07 / 071797, WO07 / 071497, WO05 / 080337, JP2010-049238, WO2008078678, JP2010-15025 and JP2010-49238, peroxy esters, such as those described in, for example, EP Benzophenone tetracarboxylic acid peroxyester in 126541, monoacylphosphine oxides, such as (2,4,6-trimethylbenzoyl)diphenylphosphine oxide (Omnirad TPO), ethyl (2,4,6-trimethylbenzoylphenyl)phosphinate;Bisacylphosphine oxides, such as bis(2,6-dimethoxybenzoyl)-(2,4,4-trimethylpentyl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Omnirad 819), bis(2,4,6-trimethylbenzoyl)-2,4-dipentyloxyphenylphosphine oxide, triacylphosphine oxide, halomethyl triazines, for example 2-[2-(4-methoxyphenyl)-vinyl]-4,6-bis-trichloromethyl-[1,3,5]triazine, 2-(4-methoxyphenyl)-4,6-bis-trichloromethyl-[1,3,5]triazine, 2-(3,4-dimethoxyphenyl)-4,6-bis-trichloromethyl-[1,3,5]triazine, 2-methyl-4,6-bis-trichloromethyl-[1,3,5]triazine, hexaarylbiimidazole / coinitiator systems, for example o-chlorohexaphenylbisimidazole in combination with 2-mercaptobenzothiazole, ferrocene compounds or titanocenes, for example bis(cyclopentadienyl)-bis(2,6-difluoro-3-pyrrolylphenyl)titanium (Omnirad 784). In addition, borate compounds, such as those described in US 4772530, EP 775706, GB 2307474, GB 2307473 and GB 2304472. The borate compounds are preferably used in combination with electron acceptor compounds such as dye cations or thioxanthone derivatives. ;
[0196] Omnirad compounds are available from IGM Resins BV. The compound is available from BASF SE.
[0197] Other examples of additional photoinitiators are peroxide compounds, such as benzoyl peroxide (other suitable peroxides are described in US Pat. No. 4,950,581, column 19, lines 17-25), or cationic photoinitiators, such as aromatic sulfonium or iodonium salts, such as those in US Pat. No. 4,950,581, column 18, line 60 to column 19, line 10, or cyclopentadienyl-arene-iron(II) complex salts, such as (η 6 -isopropylbenzene)(η 5 -cyclopentadienyl)iron(II) hexafluorophosphate.
[0198] After step c), the composition can be solvent-free or solvent-containing. Which variant is used generally depends on the method of application of the film.
[0199] The solids content of the composition obtained after step c) may therefore be from 100 to 5% by weight, based on the entire composition.
[0200] The method comprises the following step c2) after step c):
[0201] c2) Adding a solvent (S) to the mixture obtained in step c).
[0202] The solvent (S) that can be added in step c2) is selected from: alcohols, which preferably contain 1 to 6 carbon atoms, such as methanol, ethanol, 1-propanol, 2-propanol, butanol and ethylene glycol; ether alcohols, such as 2-methoxypropanol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, dipropylene glycol monomethyl ether, diethylene glycol ethyl ether and tetrahydrofurfuryl alcohol; ketones, such as acetone, 2-butanone, cyclopentanone, cyclohexanone; esters, such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl acetate, methyl formate; and ethers, such as ethyl ether and THF, preferably an alcohol, an ether alcohol or a ketone.
[0203] Mixtures of up to 5 organic solvents may be used, preferably no more than 3 organic solvents are used. In another embodiment, only one organic solvent is used.
[0204] In the case of solvent-based systems, the solids content of the composition obtained after step c) is preferably from 40 to 5% by weight, based on the entire composition, more preferably from 25 to 10% by weight, based on the entire composition.
[0205] Therefore, preferably, the solid content of the composition obtained after step c) is preferably 100 wt % or 40-5 wt %, more preferably 100 wt % or 25-10 wt %, based on the entire composition.
[0206] Typically, the solids content remains unchanged after step c) until step d) is carried out.
[0207] Preferably, however, after step c), the solids content is adjusted by dilution with a solvent to obtain a specified film thickness before step d).
[0208] The solid content before step d) is preferably not more than 75% by weight, more preferably not more than 55% by weight. Generally, the lower limit of the solid content before step d) is preferably 0.5% by weight.
[0209] The temperature during step c) and before carrying out step d) generally does not exceed 150°C, more preferably does not exceed 130°C.
[0210] The reaction time is usually less than 10 days, preferably 30 minutes to 5 days.
[0211] It is also possible to add a different compound than (OR 3 ) of the ligand (L). Usually, in this case, step b2a) is not carried out.
[0212] Thus, in one variant, step b1a) is performed instead of step b2a). This variant may comprise the following steps c3) and c4) performed after step c):
[0213] c3) heating the mixture obtained after step c), preferably heating to not higher than 150° C., more preferably
[0214] Temperature not higher than 130℃;
[0215] c4) optionally adding a different from (OR 3 )'s ligand (L).
[0216] In case step c4) is present, the reaction time of step c4) is generally less than 10 days, preferably from 2 hours to 5 days.
[0217] In the absence of steps c3) and c4), the temperature during step c) and before carrying out step d) generally does not exceed 75°C, more preferably does not exceed 50°C.
[0218] Optional (meth)acrylate (ME)
[0219] As described above, optionally, the (meth)acrylate (ME) is added at the following times:
[0220] - during the preparation of the first precursor composition (FPC),
[0221] - during the preparation of the second precursor composition (SPC), and / or
[0222] - during step c) or after step c) and before carrying out step d).
[0223] The (meth)acrylate (ME) preferably has an average molecular weight of 150 to 5000 g / mol, more preferably 250 to 1500 g / mol, even more preferably 250 to 1000 g / mol.
[0224] The (meth)acrylate (ME) is preferably an ester of a diol or polyol including polymeric diols and polyols.
[0225] The diol or polyol is preferably selected from C 2 -C 10 diol or polyol, more preferably selected from C 2 -C 6 diol or polyol, even more preferably selected from C 2 -C 4Diols or polyols, for example ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanol, for example ethylene glycol and / or diols or polyols having more than 10 carbon atoms and comprising at least one aromatic moiety, for example dihydroxybenzene, dimethylbiphenyl, bisphenol A, other mono-, di-, tri- or tetra-acrylates can also be used, for example trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, di(trimethylolpropane) tetraacrylate, pentaerythritol tetraacrylate, trimethylolpropane ethoxylate triacrylate, bisphenol A ethoxylate diacrylate, 1,6-hexanediol diacrylate, dihydroxybenzene, dimethylbiphenyl, bisphenol A.
[0226] Thus, in the case where the (meth)acrylate (ME) is an ester of a diol or polyol, including polymeric diols and polyols, one end group is a (meth)acrylate. Preferably, in this variant, the other end group does not contain an OH moiety, more preferably, the (meth)acrylate (ME) does not contain an OH moiety.
[0227] Preferably the terminal group is a monoalcohol, for example an alcohol containing an aromatic moiety, such as phenol, phenylphenol, naphthol.
[0228] Preferably, the (meth)acrylate (ME) is selected from the compounds of the following formulae (V) and (VI):
[0229] TG-O-R 12 -O] p -TG(V)
[0230] TG-[OR 12 ] p -OAO-[R 12 -O] p -TG(VI)
[0231] in:
[0232] R 12 Selected from C 2 -C 6 diols, even more preferably selected from C 2 -C 4 diols, such as ethylene glycol, 1,2-propylene glycol,
[0233] 1,3-propanediol, 1,4-butanol, such as ethylene glycol;
[0234] p is each independently selected from 1-20, more preferably 1-10, even more preferably 1 or 2;
[0235] A is a diol having more than 10 carbon atoms and preferably containing one or more aromatic moieties, for example dihydroxybenzene, dimethylbiphenyl, bisphenol A;
[0236] Each TG is independently selected from a vinyl ether group or a (meth)acrylate group or a monoalcohol, such as an alcohol containing an aromatic moiety, such as phenol, phenylphenol, naphthol, with the proviso that at least one TG is a (meth)acrylate group.
[0237] Preferably, in formula (V), one TG is selected from (meth)acrylate groups, such as acrylate groups, and the other TG is selected from alcohols containing aromatic moieties, such as phenol, phenylphenol, naphthol, such as phenylphenol.
[0238] Preferably, in formula (VI), both TGs are selected from (meth)acrylate groups, such as acrylate groups.
[0239] Preferably, the (meth)acrylate (ME) is added at the following times:
[0240] - during the preparation of the second precursor composition (SPC), or
[0241] - during step c) or after step c) and before carrying out step d).
[0242] When (meth)acrylate (ME) is added during the preparation of the second precursor composition (SPC), the total amount of (meth)acrylate (ME) is preferably 2-50 wt %, more preferably 2-40 wt %, based on the total solid content of the second precursor composition (SPC).
[0243] In case (meth)acrylate (ME) is added during step c) or after step c) and before carrying out step d), the total amount of (meth)acrylate (ME) is preferably 1 to 40% by weight, more preferably 1 to 30% by weight, based on the total amount of the solids content of the mixture before carrying out step d).
[0244] Preferably, no (meth)acrylate (ME) is added during the preparation of the first precursor composition (FPC) and before carrying out step c).
[0245] Step d)
[0246] In step d), a thin film layer is formed on a substrate.
[0247] Liquid phase atmospheric pressure film deposition and optional patterning
[0248] The film can be deposited onto the substrate using dip coating, slit coating, combined slit coating + spin coating, spin coating, spray coating, inkjet printing, curtain coating, roller coating, roll-to-roll, screen printing or using a rod, brush or by rubbing, more preferably by spray coating, slit coating, dip coating, spin coating, most preferably by spray coating and spin coating (to mention a few typical liquid deposition methods, but not limited thereto). In addition, the film can be patterned by photolithography (or other patterning methods, such as gravure printing, printing, inkjet, 3D / 4D printing, etc.) by direct patterning. By the present invention, materials suitable for producing films and structures are provided. Layers can be deposited on various substrate surfaces, such as glass, quartz, silicon, silicon nitride, polymers, metals and plastics, such as organic or inorganic semiconductor materials, and LED or OLED layers.
[0249] In addition, the material can be deposited on a large number of different surfaces, such as different oxides, doped oxides, semi-metals, layers in TFTs, layers in OLEDs and LEDs, etc. The optional patterning / structuring of the heat and / or radiation sensitive material composition can be implemented by direct photolithography patterning, conventional photolithography mask and etching procedures, imprinting and embossing (but not limited to these). The composition can be used to prepare layers that are cured at lower processing temperatures (e.g., 80°C or lower) but are stable at temperatures of up to 450°C. Therefore, the layer formed by the composition can also be cured at higher temperatures, i.e., temperatures above 230°C and up to 450°C. In this case, the film or structure made from the composition can be combined with a subsequent high temperature deposition step, such as sputtering, baking, thermal evaporation and / or CVD methods. Depending on the substrate used, the material is typically cured on a hot plate, cured in a convection oven, cured by IR lamp curing, or cured by forced air curing at 80-450°C. Also particularly in the case of material layers deposited directly on substrates already connected to display device substrates or other substrates that can withstand low curing temperatures, the processing temperature is limited to a maximum of 100°C or even to temperatures below 80°C.
[0250] Step e)
[0251] In case a solvent is present in step d), in step e), preferably after step d), the solvent is partially or completely removed.
[0252] Removal is usually performed by vacuum drying and / or thermal drying. Vacuum drying can be performed at a pressure of 10-300 Pa, preferably at a pressure of 15-200 Pa. Thermal drying (prebaking) can be performed at a temperature of 50-150°C, preferably at a temperature of 60-100°C.
[0253] Step f)
[0254] In step f), the intermediate product obtained in step e) (if present) or in step d) (if step e) is absent) is solidified.
[0255] Curing is typically carried out by exposure to heat, such as by using a convection oven, hot plate or IR radiation.
[0256] The temperature for curing is generally no more than 450°C, preferably no more than 400°C, more preferably no more than 300°C, most preferably no more than 250°C.
[0257] The curing time is generally 1.0 minute to 5.0 hours, preferably 5.0 minutes to 3.0 hours, and most preferably 10 minutes to 1.0 hour.
[0258] The film thickness after step f) is preferably at least 50 nm, more preferably at least 100 nm, most preferably at least 150 nm. Typically, the film thickness after step f) is not higher than 20 μm, preferably not more than 15 μm, most preferably not more than 10 μm.
[0259] Typically, during steps d) to f), the maximum temperature is below 450° C., preferably below 300° C., more preferably below 250° C. In certain embodiments, during steps d) to f), the maximum temperature may be 100° C. or even below 80° C. Typically, during steps d) and f), the temperature is not below 20° C.
[0260] As mentioned above, the simplest way to apply and cure a thin film coating to produce a film on a substrate can be, for example, slot coating, inkjet printing or spin coating (or in the case of inkjet also a printed structure), followed by heat curing only, combined heat + UV curing or UV curing only. Below, we will give a more detailed description of an exemplary method of coating deposition that also includes optional photolithographic patterning.
[0261] Exemplary Methods of Deposition and Optional Patterning of Coatings on Substrates:
[0262] 1. Substrate pre-cleaning: Potassium hydroxide (KOH) pre-cleaning (KOH solution can be at room temperature or the temperature can vary between 20-55°C; typical concentration can vary between 0.04-1%), followed by UV cleaning and deionized water rinsing, followed by a drying process. Alternatively, adhesion promoters, primers or other chemical or physical (e.g. plasma ashing) surface modification methods can be used to improve wetting and adhesion.
[0263] 2. Material deposition: The coating is deposited on the substrate by using slot coating, combined slot coating + spin coating, spin coating, spray coating, inkjet printing, curtain coating, roll coating, roll to roll, printing (to mention a few typical liquid deposition methods). The formulation (solvent + additives) is adjusted in a way to achieve appropriate coating thickness, uniformity and planarization / conformality of the coating (to mention a few typical requirements).
[0264] 3. Vacuum drying and / or pre-baking: After deposition, the substrate is transferred to a vacuum drying station and / or pre-baked on a hot plate (or oven) typically at 70-120°C for 1-3 minutes. In this step, the major part of the formulation solvent is removed and the substrate is left with a pre-cured film ready for further processing. Obviously, pre-baking is optional for UV-curing-only processes.
[0265] 4. Exposure: In standard photolithography methods, a photomask or intermediate mask is used together with broadband, g-line, h-line or i-line exposure. When using g-line, h-line, i-line exposure, the typical UV exposure dose required is 50-200mJ (or higher). In the case where the deposited layer does not need to be patterned or the patterning is completed by other means, full substrate area exposure can be used (without the use of any photomask or intermediate mask). The so-called waiting step or post-exposure baking step can also be used to improve the curing of the exposed area. The materials described in the present invention can act as negative toning resists, which means that the exposed areas are polymerized under UV light (this makes the exposed areas less soluble in the developer). In the case where patterning is not required, materials as thermally curable formulations can also be used without UV exposure. In this case, latent thermal initiators can be used.
[0266] 5. Development (in case of application of photolithographic patterning): In the development step, the more soluble areas of the film are dissolved by a developer solution (see above). The less soluble areas (in the case of negative toning materials, the exposed areas) remain on the substrate after development. A so-called spray development or buddle development method can be used. The developer solvent may be at room temperature or the temperature may vary between 20-55°C. Typical developers include potassium hydroxide (KOH) and tetramethylammonium hydroxide (TMAH), but are not limited to these. Typical concentrations are, for example, 0.04-0.7% for KOH and 0.2-2.38% for TMAH. Application of the developer solution is followed by rinsing of the spray or bud with deionized or standard water. As a final step, the water is dried by air knife / blowing and / or heating (blowing or IR curing, hot plate or oven).
[0267] 6. Final cure: Depending on the substrate and other coating layers used, the material is cured in a convection oven, by IR lamp curing, forced air curing at 80-300°C or in the case of UV-only curing, deposition is followed by UV exposure only without any thermal curing.
[0268] Also in particular, in the case of a material layer deposited directly on a substrate already connected to a display substrate, the processing temperatures are limited to a maximum of 100° C. or even to temperatures below 80° C. Typical curing times at this temperature may be, for example, 30 minutes.
[0269] The thickness of the film (or patterned structure) after final curing can be 10nm to 15μm. Typically, for example in the case of a bottom-emitting OLED device, the required thickness from the outcoupling layer can be 50-500nm. In the case of a top-emitting OLED device structure, the layer thickness requirement can be 1-10μm. In the case of optical films, the requirement is typically 10-200nm.
[0270] Multi-layer structure
[0271] Furthermore, the present invention relates to a multilayer structure comprising at least one layer, the at least one layer consisting of a film produced by the process according to the invention. Thus, all embodiments of the process described above also apply to the multilayer structure.
[0272] The multilayer structure may consist of 2, 3, 4, 5 or more layers and preferably less than 20 layers.
[0273] In one embodiment, the multilayer structure consists of two layers. In the embodiment, the multilayer structure consists of a layer consisting of a thin film prepared by the method of the present invention and a substrate layer, wherein one surface of the layer consisting of a thin film prepared by the method of the present invention is in direct contact with one surface of the substrate layer.
[0274] In another embodiment, the multilayer structure consists of more than two layers. Preferably, the multilayer structure consists of 3, 4, 5, 6 or 7 layers, preferably 4, 5 or 6 layers.
[0275] In the embodiment described, the multilayer structure preferably consists of a layer consisting of a film prepared by the method of the present invention, a substrate layer and 1, 2, 3, 4 or 5, preferably 2, 3 or 4 other layers. The other layers may be the same as or different from the layer consisting of the film prepared by the method of the present invention. Preferably, the other layers are different from the layer consisting of the film prepared by the method of the present invention.
[0276] Thus, preferably, one surface of the layer consisting of the thin film prepared by the method of the present invention is in direct contact with one surface of the substrate layer. Another surface of the layer consisting of the thin film prepared by the method of the present invention is in direct contact with one surface of another layer, which may be the same as or different from the layer consisting of the thin film prepared by the method of the present invention, preferably different.
[0277] In said embodiment, the layer consisting of the film produced by the process of the invention is sandwiched between a substrate layer and another layer.
[0278] The surfaces of the optional one or more additional further layers may be in direct contact with the surfaces of the further layers and / or with the surface of the substrate layer, preferably only in direct contact with the surfaces of the further layers.
[0279] The substrate layer may be any layer suitable for deposition with a layer consisting of a thin film prepared by the method of the present invention. The substrate layer may be an organic or inorganic layer. Preferably, the substrate layer is selected from glass, quartz, silicon, silicon nitride, polymers, metals and plastics, such as organic or inorganic semiconductor materials, and layers of LEDs or OLEDs, which are optionally deposited with metal circuits such as thin film transistor (TFT) circuits.
[0280] The optional further layer may be any layer suitable for preparing the multilayer structure of the present invention. The optional further layer may be an organic layer, an inorganic layer or a metallic layer.
[0281] Products
[0282] Furthermore, the invention relates to an article comprising a film obtainable by the process according to the invention or a multilayer structure according to the invention.
[0283] The article is preferably selected from:
[0284] Optical and electrical coatings;
[0285] High-k dielectrics;
[0286] light output coupling / extraction layer;
[0287] Etch and CMP stop layers;
[0288] OLED protection / sealing / encapsulation coatings;
[0289] Organic solar cells; and
[0290] Optical thin film filters.
[0291] The films of the invention can be used as optical layers on substrates, as a single optical layer or as part of a multilayer optical stack. Typical uses are to improve outcoupling or incoupling of light in device structures.
[0292] For example, the film of the present invention is deposited directly on a substrate (e.g., a glass or plastic substrate) of a bottom-emitting organic light-emitting diode (OLED) device, for example, directly on a thin-film transistor (TFT) structure. The TFT is typically part of a display device to drive each OLED pixel. For a top-emitting OLED, the output coupling layer should be processed directly on the top electrode or alternatively as part of a TFE (thin film encapsulation) stack. Here, ideally, the high refractive index output coupling layer is applied between two or more inorganic layers (i.e., SiNx). The application of the high refractive index organic layer can preferably be applied by inkjet printing. In order to build the actual OLED on the TFT circuit, the output coupling layer can be processed directly on the electrode material (e.g., indium tin oxide, ITO), which is processed directly on the TFT (or its planarization / passivation layer) or alternatively directly on top of the color filter in certain designs. In a bottom-emitting OLED device structure, the film of the present invention must withstand a curing temperature of up to 250°C, because the subsequent ITO layer deposition is usually performed at a higher temperature (low temperature deposition methods can also be used). More importantly, since all sensitive OLED device layers will be deposited on top of the thin film layers, it is necessary to have very low outgassing from the thin film layers during subsequent device layer deposition steps and during the lifetime of the device.
[0293] Figure 1 A simplified cross section of a bottom emission OLED device is shown. A TFT circuit has been deposited on the substrate (100). As a next step, a material film (110) is applied to the TFT substrate (100), which may or may not contain a color filter (color filter on array, COA design), followed by the deposition of the OLED layer (120). After the deposition of the OLED layer, the device can be completed by depositing the device encapsulation layer (130). The refractive index and film thickness requirements of the material coating (110) are defined by the optics of the TFT substrate (100) and the OLED layer (120) design to maximize the output coupling of light emitted from the OLED device layer pixels that passes through the TFT substrate to improve device efficiency. In a bottom emission OLED device structure, the cathode of the OLED layer is opaque and therefore reflects the emitted light downward (see Figure 1 The material coating (110) can also be used to adjust the possible microcavity effect to improve the device efficiency.
[0294] OLED devices can also be lighting panels, in which case the driver circuit can be much simpler, and in this case, the layer of the material of the present invention can be deposited directly on the device substrate (e.g., a glass or plastic substrate) rather than on the thin film transistor structure. As earlier, the film of the present invention again acts as an output coupling enhancement layer (improving the external efficiency of the device), but at the same time can act as a scattering layer, which can be a design requirement in the case of lighting panel applications. In this case, the material coating is used to connect the substrate and introduce scattering particles into the thin film coating formulation. Of course, multilayer methods with and without scattering can be combined to obtain the desired effect. Such particles generally provide additional optical effects, for example to meet specific needs, such as for lighting applications. These particles can be, for example, SiO 2 、TiO 2 、ZrO 2 Or similar inorganic particles.
[0295] In top emission OLED structures, the film of the present invention acts as an optical layer, but can also act as an encapsulation layer. The film can be used as an inorganic thin film encapsulation layer as part of a complete thin film encapsulation stack. Typically, 3-10 layers are used for encapsulation. In addition, the film of the present invention can also act as a planarization layer on top of the OLED (to help the subsequent thin film encapsulation (TFE) layer deposition) and also allows the adjustment of possible microcavity effects to improve the efficiency of the device.
[0296] Because the pixel density of display devices increases due to the demand for higher resolution, the planarization layer can help reduce particle defects, which can usually be caused by vacuum vapor deposition of inorganic TFE layers of a certain thickness. In addition, since the thin film layer of the present invention does not contain particles, it does not itself produce any particle defects in the thin film stack, which is a potential big problem in the case of the prior art, in which nano / micro particles are mixed in a polymer matrix and always have some particle agglomerates, which will become the source of defects in the device and its service life attenuation. The thin film encapsulation layer is also broken into thinner single layers of a maximum of 2-4μm thick, which will help maintain the flexibility of the structure, thereby allowing flexibility of the device structure.
[0297] Figure 21 shows a simplified cross-section of a top emission OLED device. In a top emission structure, the OLED layers (210) (e.g., anode / hole transport layer / emission layer / electron transport layer / cathode) are first deposited on the TFT substrate (200). One or more material coatings (220) are deposited on the OLED layers (210). After the material coatings (220) (optional cover layers, which may be HRI materials of the present invention), the device encapsulation layers (230), (240), (250) are deposited. Typically, layers 230 and 250 are very thin inorganic layers, such as silicon nitride, and layer 240 is the HRI material of the present invention, sometimes referred to as a particle cover layer (PCL). The material coatings may be part of the encapsulation layer, or even in some configurations, it may be preferred that the material coatings may be preferably deposited as the last layer after the encapsulation layer (various configurations including (230) and (240) are contemplated). In the structure shown, the OLED device is a top emission structure in which light emission is transmitted through the encapsulation layer (see Figure 2 direction of the arrow in the figure).
[0298] exist Figure 3 Another possible structure related to OLED is drawn in . In the top emission structure, the OLED layer (310) (e.g., anode / hole transport layer / emission layer / electron transport layer / cathode) is first deposited on the TFT substrate (300). One or more material coatings (320) are deposited on the OLED layer (310). After the material coating (320), the device encapsulation layers (330), (340), and (350) are deposited. Typically, layers 330 and 350 are very thin inorganic layers, such as silicon nitride, and layer (340) is the HRI material of the present invention, sometimes referred to as a particle cover layer (PCL). The material coating can be part of the encapsulation layer, or even in some configurations, it may be preferred that the material coating can be preferably deposited as the last layer after the encapsulation layer (various structures including (330) and (340) can be envisioned). And the inorganic (330) and material coatings (340) can be applied multiple times to achieve the best results for water / oxygen inhibition or light effects. In the structure shown, the OLED device is a top emission structure, in which light is emitted through the encapsulation layer (see Figure 3 direction of the arrow in the figure).
[0299] Furthermore, in the case of a top-emitting OLED structure, it is preferred that the optical and FTE layers can be processed by using inkjet printing or a combined slot coating and inkjet printing method. This ultimately allows for reduced resource input and lower production costs.
[0300] Preferred variants and embodiments of the process according to the invention and of the multilayer structure according to the invention are also preferred variants and embodiments of the article according to the invention.
[0301] Composition
[0302] Furthermore, the present invention relates to a composition comprising a first precursor composition (FPC) being one or more polymeric metal or metalloid compounds according to formula (I):
[0303] M 1 (OR 1 ) n R 2 m (I)
[0304] in:
[0305] M 1 is a metal or metalloid with a valence state z,
[0306] R 1 Each independently selected from C 1 -C 10 an organic group or an organic heteroatom group,
[0307] R 2 Each independently selected from C 1 -C 20 an organic group or an organic heteroatom group,
[0308] n is 1 to z-1,
[0309] m is 1 to z-1,
[0310] n+m is z;
[0311] wherein the polymerization is carried out by at least partial hydrolysis of M 1 (OR 1 ) structural part;
[0312] The second precursor composition (SPC) can be obtained by:
[0313] b1a) providing a metal or metalloid compound according to the following formula (II):
[0314] M 2 (OR 3 ) o (II)
[0315] in
[0316] M 2 is a metal or metalloid with a valence state y, where M 1 and M 2 Based on the different elements of the periodic table,
[0317] R 3 Each independently selected from C 1 -C 10an organic group or an organic heteroatom group,
[0318] o is y;
[0319] b2a) optionally, mixing a metal or metalloid compound according to formula (II) with a metal or metalloid compound different from (OR 3 ) ligand (L)
[0320] reaction; or
[0321] b1b) directly provides the reaction product of step b2a).
[0322] Preferred features of the methods of the invention are also preferred features of the compositions of the invention.
[0323] Furthermore, the present invention relates to a kit of parts comprising a first precursor composition (FPC) in a first container and a second precursor composition (SPC) in a second container, the first precursor composition (FPC) being one or more polymeric metal or metalloid compounds according to formula (I):
[0324] M 1 (OR 1 ) n R 2 m (I)
[0325] in:
[0326] M 1 is a metal or metalloid with a valence state z,
[0327] R 1 Each independently selected from C 1 -C 10 an organic group or an organic heteroatom group,
[0328] R 2 Each independently selected from C 1 -C 20 an organic group or an organic heteroatom group,
[0329] n is 1 to z-1,
[0330] m is 1 to z-1,
[0331] n+m is z;
[0332] wherein the polymerization is carried out by at least partial hydrolysis of M 1 (OR 1 ) structural part;
[0333] The second precursor composition (SPC) can be obtained by:
[0334] b1a) providing a metal or metalloid compound according to the following formula (II)
[0335] M 2 (OR 3 ) o (II)
[0336] in
[0337] M 2 is a metal or metalloid with a valence state y, where M 1 and M 2 Based on the different elements of the periodic table,
[0338] R 3 Each independently selected from C 1 -C 10 an organic group or an organic heteroatom group,
[0339] o is y;
[0340] b2a) optionally, mixing a metal or metalloid compound according to formula (II) with a metal or metalloid compound different from (OR 3 ) ligand (L)
[0341] reaction; or
[0342] b1b) directly provides the reaction product of step b2a).
[0343] Preferred features of the methods and compositions of the invention are also preferred features of the kits of parts of the invention.
[0344] Furthermore, the invention relates to the use of a composition or a kit of parts according to the invention for producing a film on a substrate.
[0345] Furthermore, the invention relates to the use of a composition or a kit of parts according to the invention for producing an optical or electrical coating.
[0346] Furthermore, the present invention relates to the use of the composition according to the invention for the preparation of:
[0347] -Optical and electrical coatings;
[0348] - High-k dielectrics;
[0349] - Light outcoupling / extraction layer;
[0350] - Etch and CMP stop layers;
[0351] -OLED protection / sealing / encapsulation coating;
[0352] - organic solar cells; or
[0353] -Optical thin film filters.
[0354] Figure 1 A simplified cross section of a bottom-emitting OLED device is shown.
[0355] Figure 2 A simplified cross section of a top-emitting OLED device is shown.
[0356] Figure 3 Shown is a simplified cross section of a top-emitting OLED device with a thin-film encapsulation layer.
[0357] Figure 4 A transmittance graph of the film obtained in Application Example 19 is shown (the spectrum includes the glass substrate).
[0358] Figure 5 The transmittance graph of the film obtained in Application Example 24 is shown (minus the glass substrate).
[0359] Figure 6 The weight loss determined by thermogravimetric analysis (TGA) of Application Example 24 is shown.
[0360] Experimental Section
[0361] Measurement method
[0362] The molecular weight of the polymer obtained after step a2)
[0363] The tool used for measuring the molecular weight is WATERS GPC (Gel Permeation Chromatography): Waters 1515 Isocratic HPLC pump, Waters 2414 Refractive Index Detector. Polystyrene standards are used as calibration standards for the measurement. The actual sample for measurement is prepared as a 4m-% sample using THF as the elution solution.
[0364] Solid content
[0365] The tool used for determining the molecular weight was a Mettler Toledo HB43 Halogen dessicator balance. The samples were weighed on an aluminum pan / cup and approximately 1 g of material was used for the measurement.
[0366] Shelf life determination
[0367] For actual measurement data, see Application Examples 24 and 24C. The material shelf life is determined by the following material process / application result stability / repeatability of the cured film. The values monitored by the cured film are film thickness and film refractive index. The film thickness and refractive index are characterized by using an ellipsometer (UVISEL-VASE Horiba Jobin-Yvon). Gorilla Glass 4 or silicon wafer (diameter: 150 mm, type / dopant: P / Bor, orientation: <1-0-0>, resistivity: 1-30 Ω·cm, thickness: 675+ / -25 μm, TTV: <5 μm, particles: <20 at 0.2 μm, front: polished; back: etched, flatness: 1 SEMI standard) is used as a substrate for measurement. Material film deposition is performed by using spin coating, pre-curing using a hot plate, UV exposure by a broadband UV source, and final baking in a convection oven. Optionally, the material can be UV-cured only or thermally cured only.
[0368] Viscosity
[0369] Tool manufacturer: Grabner Instruments Viscometer MINIVIS-II. Measuring method “Falling ball viscosity measurement”. The samples are measured at 20° C. by using a steel ball with a diameter of 3.175 mm.
[0370] Transmittance
[0371] Konica Minolta spectrophotometer CM-3700A (SpectraMagic NX software). The preparation of the samples is described in the examples.
[0372] Color and Haze Measurement
[0373] L*(D65), a*(D65), b*(D65) and haze were determined using a Konica Minolta spectrophotometer CM-3700A (SpectraMagic NX software). The measurements were performed using Gorilla Glass 4 as the substrate. Material film deposition was performed using spin coating, pre-curing using a hot plate, UV exposure by a broadband UV source, and final baking in a convection oven. Optionally, the material can be UV cured only or thermally cured only. Also optionally, the material is inkjet deposited on the glass.
[0374] Refractive Index
[0375] The film refractive index is characterized using an ellipsometer (UVISEL-VASE Horiba Jobin-Yvon). Gorilla Glass 4 or silicon wafers (diameter: 150 mm, type / dopant: P / Bor, orientation: <1-0-0>, resistivity: 1-30 Ω·cm, thickness: 675+ / -25 μm, TTV: <5 μm, particles: <20 at 0.2 μm, front: polished; back: etched, flatness: 1 SEMI standard) are used as substrates for measurement. Material film deposition is performed by using spin coating, pre-curing using a hot plate, UV exposure by a broadband UV source, and final baking in a convection oven. Optionally, the material can be UV-cured only or thermally cured only. Also optionally, the material is inkjet deposited on glass.
[0376] Film thickness
[0377] The film thickness was measured by using an ellipsometer (UVISEL-VASE Horiba Jobin-Yvon). Gorilla Glass 4 or silicon wafers (diameter: 150 mm, type / dopant: P / Bor, orientation: <1-0-0>, resistivity: 1-30 Ω·cm, thickness: 675+ / -25 μm, TTV: <5 μm, particles: <20 at 0.2 μm, front: polished; back: etched, flatness: 1 SEMI standard) were used as substrates for measurement. Material film deposition was performed by using spin coating, pre-curing using a hot plate, UV exposure by a broadband UV source, and final baking in a convection oven. Optionally, the material can be UV-cured only or thermally cured only. Also optionally, the material is inkjet deposited on the glass.
[0378] Thermogravimetric analysis (TGA)
[0379] A sample weighing 2.0 mg was placed in a Shimadzu TGA / DTA simultaneous measuring instrument DTG-60A, and heated continuously to 160° C., 230° C., and 250° C. under a nitrogen flow atmosphere. The heating rate was 10° C. / min, and the temperature of 160° C. was maintained for 60 minutes, the temperature of 230° C. was maintained for 60 minutes, and the temperature of 250° C. was maintained for 30 minutes.
[0380] Experimental results:
[0381] Substances used:
[0382] MIRAMER M1142, o-phenylphenol oxyethylene acrylate, CAS No. 72009-86-0, MW = 268 g / mol, supplied by Miwon
[0383] MIRAMER M244, bisphenol A (ethylene oxide) 3 Diacrylate, CAS No. 64401-02-1, MW = 468 g / mol, supplied by Miwon
[0384] Embodiment 1 of the present invention
[0385] 2.34 g of methacryloxypropylmethyldimethoxysilane, 0.5 g of water, 8 g of propylene glycol monomethyl ether and 0.2 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 16 g of propylene glycol monomethyl ether was added to the reaction mixture. 5.2 g of tetraisopropyl orthotitanate was added dropwise (5 minutes) to the reaction mixture at 80° C. (Gradual and slow addition is important. Otherwise, TiO 2 The mixture was stirred at 80°C for 3 hours to obtain a transparent solution. The solid content (SC) of the obtained solution was 14% by weight.
[0386] Embodiment 2 of the present invention
[0387] The procedure of Inventive Example 1 was repeated except that 8.4 g of tetraisopropyl orthotitanate was used, resulting in a clear solution having 15 wt % of SC.
[0388] Embodiment 3 of the present invention
[0389] The procedure of Inventive Example 2 was repeated except that 0.2 g of 2,6,10-trimethyl-2,6,10-triazaundecane was used instead of trimethylamine, yielding a clear solution having 15 wt % of SC.
[0390] Embodiment 4 of the present invention
[0391] The procedure of Inventive Example 1 was repeated, except that 5.2 g of 3-glycidoxypropylmethyldimethoxysilane was used instead of methacryloxypropylmethyldimethoxysilane, yielding a clear solution having 14 wt % of SC.
[0392] Embodiment 5 of the present invention
[0393] The procedure of Inventive Example 4 was repeated except that 11 g of 3-glycidoxypropylmethyldimethoxysilane was used, resulting in a clear solution having 20 wt % of SC.
[0394] Embodiment 6 of the present invention
[0395] 4.68 g of methacryloxypropylmethyldimethoxysilane, 1.0 g of water, 16 g of propylene glycol monomethyl ether and 0.4 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 32 g of propylene glycol monomethyl ether was added to the reaction mixture. 16.8 g of tetraisopropyl orthotitanate was added dropwise (4 minutes) to the reaction mixture at 80° C. The mixture was stirred at 130° C. for 3 hours and further stirred at 130° C. for 4 hours under distillation to produce a clear solution with 17 wt % of SC.
[0396] Embodiment 7 of the present invention
[0397] 4.68 g of glycidoxypropylmethyldimethoxysilane, 1.0 g of water, 16 g of propylene glycol monomethyl ether and 0.4 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 32 g of propylene glycol monomethyl ether was added to the reaction mixture. 22 g of tetraisopropyl orthotitanate was added dropwise (8 minutes) to the reaction mixture at 80° C. The mixture was stirred at 130° C. for 3 hours and further stirred at 130° C. for 4 hours under distillation to produce a clear solution with 26% by weight of SC.
[0398] Embodiment 8 of the present invention
[0399] 9.36 g of glycidyloxypropylmethyldimethoxysilane, 2 g of water, 32 g of propylene glycol monomethyl ether and 0.8 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 64 g of propylene glycol monomethyl ether was added to the reaction mixture. 44 g of tetraisopropyl orthotitanate was added dropwise (18 minutes) to the reaction mixture at 80° C. The mixture was stirred for 3 hours at 80° C. Thereafter, the generated alcohol was removed by evaporation under reduced pressure to produce a clear solution with 31% by weight of SC.
[0400] Embodiment 9 of the present invention
[0401] The procedure of Inventive Example 1 was repeated except that 2.34 g of mercaptopropylmethyldimethoxysilane was used instead of methacryloxypropylmethyldimethoxysilane, resulting in a clear solution having 17 wt % of SC.
[0402] Embodiment 10 of the present invention
[0403] The procedure of Inventive Example 9 was repeated except that 8.4 g of tetraisopropyl orthotitanate was used, resulting in a clear solution having 16 wt % of SC.
[0404] Embodiment 11 of the present invention
[0405] 9.36 g of glycidoxypropylmethyldimethoxysilane, 2 g of water, 32 g of propylene glycol monomethyl ether and 0.8 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 64 g of propylene glycol monomethyl ether was added to the reaction mixture. 59.6 g of titanium tetra-n-butoxide was added dropwise (9 minutes) to the reaction mixture at 80° C. The mixture was stirred at 100° C. for 3 hours to produce a clear solution with 19% by weight of SC.
[0406] Embodiment 12 of the present invention
[0407] The procedure of Inventive Example 5 was repeated, wherein 6 g of ethyl acetoacetate was added to 30 g of the resulting clear solution and the resulting mixture was stirred at 25° C. for 24 hours, yielding a clear solution having 17 wt % of SC.
[0408] Embodiment 13 of the present invention
[0409] The procedure of Inventive Example 5 was repeated, wherein 12 g of ethyl acetoacetate was added to 30 g of the resulting clear solution and the resulting mixture was stirred at 25° C. for 48 hours, yielding a clear solution having 13 wt % of SC.
[0410] Embodiment 14 of the present invention
[0411] 3.12 g of glycidyloxypropylmethyldimethoxysilane, 9 g of dimethyldiethoxysilane, 2 g of water, 32 g of propylene glycol monomethyl ether and 0.8 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 64 g of propylene glycol monomethyl ether was added to the reaction mixture. 44 g of tetraisopropyl orthotitanate was added dropwise (7 minutes) to the reaction mixture at 80° C. The mixture was stirred at 100° C. for 3 hours to produce a clear solution with 16 wt % of SC.
[0412] Embodiment 15 of the present invention
[0413] The procedure of Inventive Example 11 was repeated, wherein 4 g of ethyl acetoacetate and 16 g of propylene glycol monomethyl ether were added to 20 g of the resulting clear solution and the resulting mixture was stirred at 25° C. for 72 hours, yielding a clear solution having 10 wt % of SC.
[0414] Embodiment 16 of the present invention
[0415] 2.11 g of methacrylpropyltrimethoxysilane, 0.23 g of glycidyloxypropylmethyldimethoxysilane, 0.5 g of water, 8 g of propylene glycol monomethyl ether and 0.2 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 16 g of propylene glycol monomethyl ether was added to the reaction mixture. 8.4 g of tetraisopropyl orthotitanate was added dropwise to the reaction mixture at 80° C. The mixture was stirred at 80° C. for 6 hours to produce a clear solution with 17 wt % of SC.
[0416] Embodiment 17 of the present invention
[0417] 2.34 g of glycidoxypropyltrimethoxysilane, 0.5 g of water, 32 g of propylene glycol monomethyl ether and 0.8 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 64 g of propylene glycol monomethyl ether was added to the reaction mixture. 11 g of tetraisopropyl orthotitanate was added dropwise to the reaction mixture at 80° C. The mixture was stirred at 80° C. for 20 hours to produce a clear solution with 23 wt % of SC.
[0418] Embodiment 18 of the present invention
[0419] 1.76 g of glycidyloxypropylmethyldimethoxysilane, 0.58 g of glycidyloxypropyltrimethoxysilane, 0.5 g of water, 32 g of propylene glycol monomethyl ether and 0.8 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 64 g of propylene glycol monomethyl ether was added to the reaction mixture. 11 g of tetraisopropyl orthotitanate was added dropwise to the reaction mixture at 80° C. The mixture was stirred at 80° C. for 20 hours to produce a clear solution with 21 wt % of SC.
[0420] Embodiment 19 of the present invention
[0421] Solution 1: Methacryloxypropyltriethoxysilane (120 g) was added to a reaction flask and 21 g of water (0.1 M HNO 3 ). The reaction mixture was refluxed at 95° C. in an oil bath for 3 hours and 40 minutes. The solution was cooled, and a mixture of triethylamine (0.39 g) and 2-propanol (3.51 g) was added and refluxed for 65 minutes. After reflux, the solvent was removed under reduced vacuum. The molecular weight of the material was 1000.
[0422] Solution 2: To a 80% solution of zirconium (IV) butoxide in butanol (400 g) was added ethyl acetoacetate (217.08 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure.
[0423] Mixture preparation: To a 1 L round bottom flask was added solution 1 (2.5 g), 1-methoxy-2-propanol (850 g), dipropylene glycol (50 g), solution 2 (97.5 g) and BYK333 (2.9 g). The solution was mixed at room temperature for 2 hours.
[0424] Embodiment 20 of the present invention
[0425] Solution 1: To a 70% solution of zirconium (IV) isopropoxide in 2-propanol (50 g) was added ethyl acetoacetate (83.43 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure.
[0426] Solution 2: Methacryloxypropyltriethoxysilane (36 g) was added to a reaction flask and 6.3 g of water (0.1 M HNO 3 ). The reaction mixture was stirred at room temperature for 3 days. The solvent was removed under reduced pressure. The molecular weight of the material was 1000.
[0427] Mixture preparation: Into a 500 ml round bottom flask, solution 1 (77 g), solution 2 (3 g) and Miramer M1142 (20 g) were added. The solution was mixed at room temperature for 2 hours.
[0428] Embodiment 21 of the present invention
[0429] Solution 1: To a 70% solution of zirconium (IV) isopropoxide in 2-propanol (50 g) was added ethyl acetoacetate (111.24 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure.
[0430] Solution 2: Methacryloxypropyltriethoxysilane (36 g) was added to a reaction flask and 6.3 g of water (0.1 M HNO 3 ). The reaction mixture was stirred at room temperature for 3 days. The solvent was removed under reduced pressure. The molecular weight of the material was 1000.
[0431] Mixture preparation: Into a 500 ml round bottom flask, solution 1 (77 g), solution 2 (3 g) and Miramer M1142 (20 g) were added. The solution was mixed at room temperature for 2 hours.
[0432] Embodiment 22 of the present invention
[0433] Solution 1: To a 70% solution of zirconium (IV) isopropoxide in 2-propanol (50 g) was added ethyl acetoacetate (83.43 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure. The mass of the solution after solvent removal was 96.2 g.
[0434] Solution 2: Methacryloxypropyltriethoxysilane (36 g) was added to a reaction flask and 6.3 g of water (0.1 M HNO 3 ). The reaction mixture was stirred at room temperature for 3 days. The solvent was removed under reduced pressure. The molecular weight of the material was 1000.
[0435] Mixture preparation: To a 100 ml flask, solution 1 (67 g), solution 2 (3 g), Miramer M244 (30 g) and BYK3700 (2 g) were added. The solution was mixed at room temperature for 2 hours.
[0436] Embodiment 23 of the present invention
[0437] Solution 1: To a 70% solution of zirconium (IV) isopropoxide in 2-propanol (200 g) was added ethyl acetoacetate (222.48 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure. The mass of the solution after solvent removal was 270.46 g.
[0438] Solution 2: Methacryloxypropyltriethoxysilane (36 g) was added to a reaction flask and 6.3 g of water (0.1 M HNO 3 ). The reaction mixture was stirred at room temperature for 3 days. The solvent was removed under reduced pressure. The molecular weight of the material was 1000.
[0439] Mixture preparation: To a 100 ml flask, solution 1 (67 g), solution 2 (3 g), Miramer M1142 (30 g) and BYK3700 (2 g) were added. The solution was mixed at room temperature for 2 hours.
[0440] Embodiment 24 of the present invention
[0441] Solution 1: To a 80% solution of zirconium (IV) butoxide in butanol (1963 g) was added ethyl acetoacetate (1066 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure.
[0442] Solution 2: Miramer 1142 (90 g) was added to a reaction flask and 2-propanol (60 g) and 5.1 g water (0.01 M HNO 3 The solution was stirred at room temperature for 16 hours.
[0443] Solution 3: Phenyltrimethoxysilane (5.42 g) was added to a round bottom flask and 1.42 g of water (0.01 M HNO 3 The solution was stirred at room temperature for 16 hours.
[0444] Mixture preparation: Solution 2 (155.1 g) and solution 1 (2372.0 g) were combined. 2-methoxy-1-propanol (4145.0 g) was added to the combined solution. Solution 3 (6.9 g) was added to solution 1+2. 539.49 g of 2-methoxy-1-propanol was added at the end. The solution was stirred at room temperature for 20 hours.
[0445] Embodiment 25 of the present invention
[0446] Solution 1: To a 80% solution of zirconium (IV) butoxide in butanol (1963 g) was added ethyl acetoacetate (1066 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure.
[0447] Solution 2: Miramer 1142 (90 g) was added to a reaction flask, 2-propanol (60 g) and 5.1 g water (0.01 M HNO 3 The solution was stirred at room temperature for 16 hours.
[0448] Solution 3: Phenyltrimethoxysilane (5.42 g) was added to a round bottom flask and 1.42 g of water (0.01 M HNO 3 The solution was stirred at room temperature for 16 hours.
[0449] Mixture preparation: Solution 2 (9.36 g) and solution 1 (144.0 g) were combined. 2-methoxy-1-propanol (252.0 g) was added to the combined solution. Solution 3 (0.41 g) was added to solution 1+2. 361.38 g of 2-methoxy-1-propanol was added at the end. The solution was stirred at room temperature overnight.
[0450] Embodiment 26 of the present invention
[0451] Solution 1: To a 80% solution of zirconium (IV) butoxide in butanol (1963 g) was added ethyl acetoacetate (1066 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure. Solution 2: Miramer 1142 (90 g) was added to a reaction flask, 2-propanol (60 g) and 5.1 g of water (0.01 M HNO 3 The solution was stirred at room temperature for 16 hours. Solution 3: Phenyltrimethoxysilane (5.42 g) was added to a round bottom flask and 1.42 g of water (0.01 M HNO 3). The solution was stirred at room temperature for 16 hours. Mixture preparation: Solution 1 (1244.3 g) and solution 2 (80.9 g) were combined. 2-methoxy-1-propanol (2177.9 g) was added to the combined solution. Solution 3 (3.8 g) was added to solution 1+2. At the end, 283.2 g of 2-methoxy-1-propanol was added. The solution was stirred at room temperature for 20 hours. The measured viscosity was 3.6 mPa-s. Alternatively, instead of the solvent PGME, various solvents can be used, i.e., a single solvent such as THF-A (tetrahydrofurfuryl alcohol), PGMEA, cyclohexanone, ethylene glycol, dipropylene glycol monomethyl ether, diethylene glycol ethyl ether and combinations thereof in different proportions.
[0452] Embodiment 27 of the present invention
[0453] Solution 1: To a 80% solution of zirconium (IV) butoxide in butanol (1963 g) was added ethyl acetoacetate (1066 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure. Solution 2: Miramer 1142 (90 g) was added to a reaction flask, 2-propanol (60 g) and 5.1 g of water (0.01 M HNO 3 The solution was stirred at room temperature for 16 hours. Solution 3: Phenyltrimethoxysilane (5.42 g) was added to a round bottom flask and 1.42 g of water (0.01 M HNO 3 ). The solution was stirred at room temperature for 16 hours. Mixture preparation: Solution 1 (268 g) and solution 2 (17.42 g) were combined. PGME (2-methoxy-1-propanol, 220.43 g) was added to the combined solution. 0.50 g of solution 3 was added and the final mixture was stirred at room temperature overnight. The measured viscosity was 6.9 mPa-s.
[0454] Embodiment 28 of the present invention
[0455] Solution 1: To a 80% solution of zirconium (IV) butoxide in butanol (1963 g) was added ethyl acetoacetate (1066 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure. Solution 2: Miramer 1142 (90 g) was added to a reaction flask, 2-propanol (60 g) and 5.1 g of water (0.01 M HNO 3 The solution was stirred at room temperature for 16 hours. Solution 3: Phenyltrimethoxysilane (5.42 g) was added to a round bottom flask and 1.42 g of water (0.01 M HNO 3). The solution was stirred at room temperature for 16 hours. Mixture preparation: Solution 1 (268 g) and solution 2 (17.42 g) were combined. A solvent mixture of PGMEA (1-methoxy-2-propyl acetate, 210.13 g) was added to the combined solution. 0.50 g of solution 3 was added and the final mixture was stirred at room temperature overnight. The solution viscosity was measured to be 3.9 mPa-s.
[0456] Embodiment 29 of the present invention
[0457] Solution 1: To a 80% solution of zirconium (IV) butoxide in butanol (1963 g) was added ethyl acetoacetate (1066 g). The solution was mixed at room temperature for 5 days. The solvent was removed under reduced pressure. Solution 2: Miramer 1142 (90 g) was added to a reaction flask, 2-propanol (60 g) and 5.1 g of water (0.01 M HNO 3 The solution was stirred at room temperature for 16 hours. Solution 3: Phenyltrimethoxysilane (5.42 g) was added to a round bottom flask and 1.42 g of water (0.01 M HNO 3 ). The solution was stirred at room temperature for 16 hours. Mixture preparation: Solution 1 (268 g) and solution 2 (17.42 g) were combined. A solvent mixture of PGMEA (1-methoxy-2-propyl acetate, 35.18 g) and tetrafurfuryl alcohol (82.08 g) was added to the combined solution. 0.40 g of solution 3 was added and the final mixture was stirred at room temperature overnight. The solution viscosity was measured to be 20.0 mPa-s.
[0458] Embodiment 30 of the present invention
[0459] 2.34 g of glycidoxypropylmethyldimethoxysilane, 0.5 g of water, 24 g of propylene glycol monomethyl ether and 0.2 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 12 g of tetraisopropyl orthotitanate was added dropwise to the reaction mixture at 80° C. The mixture was stirred at 100° C. for 3 hours. After cooling to room temperature, 4.6 g of chlorotrimethylsilane was added to the reaction mixture and heated at 100° C. for 1.5 hours, resulting in a clear solution with 22 wt % of SC.
[0460] Embodiment 31 of the present invention
[0461] The procedure of Inventive Example 30 was repeated except that 2.3 g of chlorotrimethylsilane was used, resulting in a clear solution having 21 wt % of SC.
[0462] Embodiment 32 of the present invention
[0463] 2.34 g of mercaptopropylmethyldimethoxysilane, 0.5 g of water, 24 g of propylene glycol monomethyl ether and 0.2 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 14.8 g of tetraisopropyl orthotitanate was added dropwise to the reaction mixture at 80° C. The mixture was stirred at 100° C. for 3 hours. After cooling to room temperature, 2.8 g of chlorotrimethylsilane was added to the reaction mixture and heated at 100° C. for 1.5 hours to produce a clear solution with 19 wt % of SC.
[0464] Embodiment 33 of the present invention
[0465] 2.34 g of mercaptopropylmethyldimethoxysilane, 0.5 g of water, 24 g of propylene glycol monomethyl ether and 0.2 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 7.4 g of tetraisopropyl orthotitanate was added dropwise to the reaction mixture at 80° C. The mixture was stirred at 100° C. for 3 hours. After cooling to room temperature, 0.25 g of water and 5.6 g of chlorotrimethylsilane were added to the reaction mixture and heated at 100° C. for 1.5 hours to produce a clear solution with 17 wt % of SC.
[0466] Embodiment 34 of the present invention
[0467] 2.34 g of glycidyloxypropylmethyldimethoxysilane, 0.5 g of water, 24 g of propylene glycol monomethyl ether and 0.2 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 12 g of tetraisopropyl orthotitanate was added dropwise to the reaction mixture at 80° C. The mixture was stirred at 100° C. for 3 hours. A mixture of 5 g of trimethylethoxysilane, 0.5 g of water, 4 g of propylene glycol monomethyl ether and 0.2 g of triethylamine was added dropwise to the reaction mixture and heated at 100° C. for 15 hours to produce a clear solution with 16 wt % of SC.
[0468] Embodiment 35 of the present invention
[0469] 2.34 g of glycidoxypropylmethyldimethoxysilane, 0.5 g of water, 24 g of propylene glycol monomethyl ether and 0.2 g of triethylamine were placed in a round bottom flask and stirred at 80° C. (oil bath) for 30 minutes. 12 g of tetraisopropyl orthotitanate was added dropwise to the reaction mixture at 80° C. The mixture was stirred at 100° C. for 3 hours. A mixture of 6.3 g of diethoxydimethylsilane, 0.5 g of water, 4 g of propylene glycol monomethyl ether and 0.2 g of triethylamine was added dropwise to the reaction mixture and heated at 100° C. for 18 hours to produce a clear solution with 17 wt % of SC.
[0470] Application Example 19
[0471] The thin film coating of Example 19 of the present invention was deposited on glass by spraying. The coating solid content was about 9.8%. The spraying parameters used to deposit this layer on Gorilla Glass 4 were as follows: scanning speed: 300 mm / s, spacing: 50 mm, gap: 50-100 mm, flow rate: 3-10 ml / min, atomization pressure: 5 kg / cm2. After spray deposition, the film was cured in a convection oven at 150°C for 30 minutes. Figure 4 The transmittance graph of the resulting material is shown. The reflection and absorption of the glass substrate were not subtracted. Other optical properties of the film include: transmittance at 550nm is 92.3%, a*(D65) 0.07 and b*(D65) 0.46. The refractive index is 1.56 (at 632nm) and the final cured thickness is 308nm.
[0472] Application Example 20
[0473] The material of Example 20 of the present invention was tested by characterizing the material on a silicon wafer (diameter: 150 mm, type / dopant: P / Bor, orientation: <1-0-0>, resistivity: 1-30 Ω·cm, thickness: 675+ / -25 μm, TTV: <5 μm, grain: <20 at 0.2 μm, front: polished, back: etched, flatness: 1 SEMI standard) and in this case spin coating was used as the deposition method. Spin coating at 2000 rpm was used as the deposition method, pre-baking at 100° C. for 120 seconds and post-baking at 100° C. for 30 minutes. The film thickness was measured to be 3.1 μm and the refractive index was 1.608 (at 632 nm).
[0474] Application Example 21
[0475] The material of Example 21 of the present invention was tested by characterizing the material on a silicon wafer (diameter: 150 mm, type / dopant: P / Bor, orientation: <1-0-0>, resistivity: 1-30 Ω·cm, thickness: 675+ / -25 μm, TTV: <5 μm, grain: <20 at 0.2 μm, front: polished, back: etched, flatness: 1 SEMI standard) and in this case spin coating was used as the deposition method. Spin coating at 2000 rpm was used as the deposition method, pre-baking at 100° C. for 120 seconds and post-baking at 100° C. for 30 minutes. The film thickness was measured to be 3.3 μm and the refractive index was 1.613 (at 632 nm).
[0476] Application Example 22
[0477] The material of Example 22 of the present invention was tested by characterizing the material on a silicon wafer (diameter: 150 mm, type / dopant: P / Bor, orientation: <1-0-0>, resistivity: 1-30 Ω·cm, thickness: 675+ / -25 μm, TTV: <5 μm, grain: <20 at 0.2 μm, front: polished, back: etched, flatness: 1 SEMI standard) and in this case spin coating was used as the deposition method. Spin coating at 2000 rpm was used as the deposition method, pre-baking at 100° C. for 120 seconds and post-baking at 100° C. for 30 minutes. The film thickness was measured to be 6.1 μm and the refractive index was 1.585 (at 632 nm).
[0478] Application Example 23
[0479] The material of Example 23 of the present invention was tested by characterizing the material on a silicon wafer (diameter: 150 mm, type / dopant: P / Bor, orientation: <1-0-0>, resistivity: 1-30 Ω·cm, thickness: 675+ / -25 μm, TTV: <5 μm, grain: <20 at 0.2 μm, front: polished, back: etched, flatness: 1 SEMI standard) and in this case spin coating was used as the deposition method. Spin coating at 2000 rpm was used as the deposition method, pre-baking at 100° C. for 120 seconds and post-baking at 100° C. for 30 minutes. The film thickness was measured to be 6.1 μm and the refractive index was 1.653 (at 632 nm).
[0480] Application Example 24
[0481] The thin film coating of Example 24 of the present invention was deposited on S2003F3 obtained from Matsunamiglass Ind., Ltd. by spin coating at 360 rpm for 30 seconds using a spin coater 1H-DX2 obtained from Mikasa Co., Ltd., Japan. Pre-baking at 100° C. for 120 seconds and post-baking at 250° C. for 30 minutes. The film thickness was measured to be 200 nm and the refractive index was 1.71 (at 632 nm). Then, 1-bromonaphthalene obtained from Wako Pure Chemical Industries, Ltd., Japan was additionally applied to the surface of the coating at a thickness of 58 μm to eliminate thin film interference effects for transmittance measurement and covered with the same slide glass plate. Figure 5 A transmittance graph of the material is shown. Other optical properties of the film include (excluding substrate): transmittance at 550 nm was 99.1%, a*(D65) -0.35 and b*(D65) 0.45.
[0482] Application of Example 24A
[0483] The procedure of Example 24 was repeated except that a post-bake step was performed four (4) times at 250°C for 30 minutes with cooling to room temperature between each bake step.
[0484] Application of Example 24B
[0485] The procedure of Example 24 was repeated except that a post-bake step was performed at 250° C. for 30 minutes and then at 350° C. for 30 minutes.
[0486] The results are given in the table below.
[0487]
[0488] In the table above, an overview is given about the stability of the material for single and multiple bake cycles. Upon increasing bake temperature, the refractive index varies between 1.71-1.87 and the film thickness decreases from 463 nm to 301 nm.
[0489] In addition, the exhaust gas of Example 24 was measured by thermogravimetric analysis (TGA). The results are shown in Figure 6 and are summarized in the table below.
[0490]
[0491] Figure 6 The above table shows that for the material of Example 24, the material has a low weight loss as determined by thermogravimetric analysis (TGA) even at elevated temperatures. The weight loss at 160°C is attributed to the removal of trace amounts of water. After removal of water, no significant weight loss was observed at 230°C and at 250°C. These are typical processing temperatures in device fabrication. Therefore, the inventive material does not produce significant outgassing during the fabrication process.
[0492] Application of Example 24C
[0493] The procedure of applying Example 24 was repeated except that the spin coating step was performed at 2000 rpm.
[0494] The thickness of the resulting films of Application Example 24 and Application Example 24C were measured over 23 weeks at +4° C. and +23° C. For Application Example 24, the difference in refractive index at +4° C. and +23° C. was also measured. The results are shown in the table below.
[0495] Film thickness of Example 24 [nm]
[0496] Day 0 5 weeks 10 weeks 23 weeks +4℃ 458 452 422 467 +23℃ 458 424 440 451
[0497] Film thickness of applied example 24C [nm]
[0498] Day 0 5 weeks 10 weeks 23 weeks +4℃ 223 214 200 218 +23℃ 223 196 202 215
[0499] The refractive index of the film of Example 24 is applied
[0500] Day 0 5 weeks 10 weeks 23 weeks +4℃ 1.710 1.707 1.710 1.71 +23℃ 1.710 1.709 1.707 1.70
[0501] The data in the table above are shelf life stability data for the material of Example 24 of the present invention. The shelf life of the ready-to-use formulation was analyzed at +4°C and +23°C. The two different spin speeds and resulting film thicknesses were analyzed over 23 weeks for film thickness consistency and refractive index consistency. From this data it can be confirmed that the material of Example 24 of the present invention is very stable at both aging temperatures.
[0502] Application Example 25
[0503] The thin film coating of Example 25 of the present invention was deposited on Gorilla Glass 4 by spin coating. The material was characterized on a glass substrate and spin coating was used as the deposition method. Spin coating at 2000 rpm was used as the deposition method, pre-baking at 100°C for 120 seconds and post-baking at 250°C. The film thickness was measured to be 56nm and the refractive index was 1.72 (at 632nm). The only difference between the materials of Examples 24 and 25 was that the material was further diluted in the case of Sample 25 to produce a thinner film.
[0504] Application Example 27
[0505] The thin film coating of Example 26 of the present invention was tested by characterizing the material on Gorilla Glass 4 and in this case using spin coating as the deposition method. Spin coating at 2000 rpm was used as the deposition method, with a pre-bake at 100° C. for 120 seconds and a post-bake at 250° C. for 30 minutes.
[0506] Application Example 28
[0507] The procedure of Example 27 was repeated except that the inventive material 28 was used.
[0508] The results are shown in the table below.
[0509] Application Example 27 Application Example 28 Thickness [nm] 409 408 Refractive index (632nm) 1.71 1.71 Δa* -0.32 0.3 Δb*(yellowing) -0.45 -0.74 L* 95.58 95.52 Transmittance (400nm) [%] 87.89 87.04 Transmittance (550nm) [%] 88.25 87.86
[0510] Application of Example 28A
[0511] The thin film coating of Example 28 of the present invention was deposited on glass by an inkjet printing coating method. The material was characterized on Gorilla Glass 4 and silicon wafers (diameter: 150 mm, type / dopant: P / Bor, orientation: <1-0-0>, resistivity: 1-30 Ω·cm, thickness: 675+ / -25 μm, TTV: <5 μm, particles: <20 at 0.2 μm, front: polished, back: etched, flatness: 1 SEMI standard) and inkjet coating was used as the deposition method. Inkjet printing (Dimatix MaterialsPrinter DMP-2850; Jets 16, jet frequency 5 kHz, applied voltage 20 V, drop spacing 30 μm, cartridge type 10 pL) was used as the deposition method, pre-baked at 100°C for 120 seconds and post-baked at 250°C for 30 minutes. The film thickness was measured to be 450 nm and the refractive index was 1.71 (at 632 nm).
[0512] Apply Example 28B and C
[0513] The thin film coating of Example 28 of the present invention is prepared by mixing scattering particles (TiO with an average particle size of 200 nm) at two different concentrations. 2 , available from Kronos) was introduced into the material for further modification. Application Example 28B was prepared by adding 3.8 wt% scattering particles by weight to the formulation of Example 28 of the present invention, and Application Example 28C was prepared by adding 4.8 wt% scattering particles to the formulation of Example 28 of the present invention. The thin film coatings of Examples 28B and 28C of the present invention were deposited on Gorilla Glass 4 by spin coating. Spin coating at 400 rpm was used as the deposition method, pre-baked at 100°C for 120 seconds, and post-baked at 250°C for 30 minutes. The film thickness was measured to be 400 nm. Other optical data of the two application examples are listed in the table below.
[0514] Application of Example 28B Application of Example 28C Thickness [nm] 400 400 Haze 15% 18% Δa* 1.21 2.52 Δb*(yellowing) -0.72 -0.47 L* 71.57 61.45 Transmittance (400nm) [%] 50.59 36.10 Transmittance (550nm) [%] 46.44 31.81
[0515] Comparative Example 1 (Compared to Examples 1-18 of the present invention)
[0516] 0.5 g of water, 24 g of propylene glycol monomethyl ether and 0.2 g of triethylamine were placed in a round bottom flask and heated at 80° C. (oil bath). A mixture of 2.34 g of methacryloxypropylmethyldimethoxysilane and 5.2 g of tetraisopropyl orthotitanate was added dropwise (3 minutes) to the reaction mixture at 80° C. A precipitate was gradually generated during the addition and the solution became translucent after the mixture was added. The reaction mixture was stirred at 80° C. for 3 hours to obtain a translucent white dispersion.
[0517] It was not possible to form a film from the composition because an opaque film was produced.
Claims
1. A method for preparing a thin film on a substrate, the method comprising the following steps: a) preparing a first precursor composition (FPC) in a first container, the preparation comprising the following steps: a1) providing one or more metal or metalloid compounds according to the following formula (I): M 1 (OR 1 ) n R 2 m (I) in: M 1 is a metal or metalloid with a valence state z, R 1 Each independently selected from C1-C 10 an organic group or an organic heteroatom group, R 2 Each independently selected from C1-C 20 an organic group or an organic heteroatom group, n is 1 to z, m is z-1 to 0, n+m is z, a2) at least partially hydrolyze M under acidic or alkaline conditions 1 (OR 1 ) moiety and polymerizing a metal or metalloid compound according to formula (I) to obtain a first precursor composition (FPC) comprising the product of step a2); wherein the molecular weight of the product of step a2) is 250-6000 g / mol; b) preparing a second precursor composition (SPC) in a second container, the preparation comprising the following steps: b1a) providing a metal or metalloid compound according to the following formula (II): M 2 (OR 3 ) o (II) in: M 2 is a metal or metalloid with a valence state y, where M 1 and M 2 Based on the different elements of the periodic table, R 3 Each independently selected from C1-C 10 an organic group or an organic heteroatom group, o is y; b2a) optionally, mixing a metal or metalloid compound according to formula (II) with a metal or metalloid compound different from (OR 3 ) of a ligand (L); or b1b) directly providing the reaction product of step b2a); c) mixing the first precursor composition (FPC) comprising the product of step a2) with the second precursor composition (SPC); c1) optionally, reacting the product of step c) with Si(R 23 )3X or Si(R 23 )2X2 reaction, wherein: R 23 is a C1-C3 alkyl group, X represents Cl or OR 24 , R 24 is a C1-C3 alkyl group; d) forming a thin layer on a substrate; e) optionally, after step d), partially or completely removing the solvent, if present; f) solidifying the intermediate product obtained in step e) if present or in step d) if no step e) is present; Wherein, optionally, (meth)acrylate (ME) is added at the following time: - during the preparation of the first precursor composition (FPC), - during the preparation of the second precursor composition (SPC), and / or - during step c) or after step c) and before carrying out step d).
2. The method of claim 1, wherein in step c), M 1 With M 2 The molar ratio is 1.0:10 to 10:1.0, preferably 1.0:10 to 1.0:1.0, and more preferably 1.0:10 to 1.0:2.
0.
3. The method of claim 1, wherein M 1 and / or M 2 Independently selected from Si, Ge, Sb, Ti, Zr, Al, Sn, W, Se, Cr, Ag or Ni.
4. The method of claim 1, wherein during step c), additives such as surfactants, leveling agents, processing aids, antistatic agents, antioxidants, water and oxygen scavengers, catalysts, scattering particles, photoinitiators or mixtures thereof are added.
5. The process according to claim 1, wherein during steps d) to f), the maximum temperature is below 450°C, preferably below 300°C.
6. The process as claimed in claim 1, wherein the process comprises, after step c), the following step c2): c2) adding a solvent (S) to the mixture obtained in step c).
7. The process of claim 1, wherein the solids content before step d) does not exceed 75% by weight, preferably does not exceed 55% by weight.
8. The process of claim 1, wherein the solids content before step d) is at least 90% by weight.
9. The method of claim 1, wherein step f) is performed by thermal and / or radiation curing.
10. A multilayer structure comprising at least one layer consisting of a film prepared by the method according to any one of the preceding claims.
11. The multilayer structure according to claim 10, wherein a surface of the at least one layer consisting of a film produced by the method according to any one of claims 1 to 10 is in direct contact with a surface of the substrate and / or another layer.
12. An article comprising a film obtainable by a process as claimed in any one of claims 1 to 9 or a multilayer structure as claimed in any one of claims 10 to 11.
13. The article of claim 12, selected from: -Optical and electrical coatings; - High-k dielectrics; - Light outcoupling / extraction layer; - Etch and CMP stop layers; -OLED protection / sealing / encapsulation coating; - Organic solar cells; and -Optical thin film filters.
14. A composition comprising a first precursor composition (FPC) and a second precursor composition (SPC), the first precursor composition (FPC) being one or more polymeric metal or metalloid compounds according to formula (I): M 1 (OR 1 ) n R 2 m (I) in: M 1 is a metal or metalloid with a valence state z, R 1 Each independently selected from C1-C 10 an organic group or an organic heteroatom group, R 2 Each independently selected from C1-C 20 an organic group or an organic heteroatom group, n is 1 to z-1, m is 1 to z-1, n+m is z; wherein the polymerization is carried out by at least partial hydrolysis of M under acidic or basic conditions 1 (OR 1 ) structural part to obtain a first precursor composition (FPC) comprising the product of step a2), wherein the molecular weight of the product of step a2) is 250-6000 g / mol; The second precursor composition (SPC) can be obtained by: b1a) providing a metal or metalloid compound according to the following formula (II): M 2 (OR 3 ) o (II) in M 2 is a metal or metalloid with a valence state y, where M 1 and M 2 Based on the different elements of the periodic table, R 3 Each independently selected from C1-C 10 an organic group or an organic heteroatom group, o is y; b2a) optionally, mixing a metal or metalloid compound according to formula (II) with a metal or metalloid compound different from (OR 3 ) ligand (L) reaction; or b1b) directly providing the reaction product of step b2a), Said composition is obtained by mixing a first precursor composition (FPC) comprising the product of step a2) with a second precursor composition (SPC).
15. A kit of parts comprising a first precursor composition (FPC) in a first container and a second precursor composition (SPC) in a second container, the first precursor composition (FPC) being one or more polymeric metal or metalloid compounds according to formula (I): M 1 (OR 1 ) n R 2 m (I) in: M 1 is a metal or metalloid with a valence state z, R 1 Each independently selected from C1-C 10 an organic group or an organic heteroatom group, R 2 Each independently selected from C1-C 20 an organic group or an organic heteroatom group, n is 1 to z-1, m is 1 to z-1, n+m is z; wherein the polymerization is carried out by at least partial hydrolysis of M under acidic or basic conditions 1 (OR 1 ) structural part and the molecular weight of the product is 250-6000g / mol; The second precursor composition (SPC) can be obtained by: b1a) providing a metal or metalloid compound according to the following formula (II) M 2 (OR 3 ) o (II) in M 2 is a metal or metalloid with a valence state y, where M 1 and M 2 Based on the different elements of the periodic table, R 3 Each independently selected from C1-C 10 an organic group or an organic heteroatom group, o is y; b2a) optionally, mixing a metal or metalloid compound according to formula (II) with a metal or metalloid compound different from (OR 3 ) ligand (L) reaction; or b1b) directly provides the reaction product of step b2a).
16. Use of a composition according to claim 14 or a kit of parts according to claim 15 for producing a film on a substrate and / or for producing: -Optical and electrical coatings; - High-k dielectrics; - Light outcoupling / extraction layer; - Etch and CMP stop layers; -OLED protection / sealing / encapsulation coating; - Organic solar cells; or -Optical thin film filters.
Citation Information
Patent Citations
Photopolymerization initiator and method of photopolymerization by use of said initiator
EP0126541A1
Borates photoinitiators from polyboranes
EP0775706A2
Method of synthesizing hybrid metal oxide materials and applications thereof
EP1761462B1
Shuttered electrical terminal
GB2304472A
Organo-boron photoinitiators
GB2307473A